Emergence in the WAEMU and EMCCA areas - Ntwali, Valéry IRAGI; Centwali, Guillain CIRHUZA (Studia Universitatis Babeș-Bolyai Studia Europaea, 2021)
The Economic and Monetary Community of Central Africa (EMCCA) and the West African Economic and Monetary Union (WAEMU) have succeeded in stabilizing their monetary systems, but this monetary stability has not been accompanied by real emergence. The economies of most of the member states of these two organizations are based on commodities and cocoa, which means that they are completely volatile and therefore lack the stability necessary for real emergence. This study based mainly on documentary research through the exploitation of reports produced by various international and regional institutions such as the IMF, the World Bank, the African Development Bank, ECOWAS, etc., and the writings of various emergence theorists, shows the role that industrialization and diversification of the economies of the WAEMU and EMCCA zones should play in the development of the economies of the member states and the improvement of the living conditions of the populations.
Keywords: CEMAC; Emergence; Spaces; UEMOA; WAEMU

التضامن الداخلي كنظام إستثنائي ينفرد به قانون الصرف دون غيره من القوانين - بوخاتم, مولياط (مجلة البحوث في الحقوق والعلوم السياسية, 2021)
بالإضافة إلى التضامن الخارجي الذي يربط الموقعين على الورقة التجارية بالحامل، أقام المشرع ضربا من التضامن الداخلي بين الموقعين ببعضهم البعض، فأجاز القانون لكل موقع قام بوفاء قيمة هذه الورقة أن يرجع على مختلف الموقعين منفردين أو مجتمعين بكل ماأوفاه دون أن يتحمل نصيبا معينا متمتعا بجميع الحقوق الناشئة عن هاته الورقة التي كان الحامل السابق يتمتع بها، غير أن هذا الرجوع الذي يقوم به الموفي لايكون إلا على الضامنين السابقين عليه في التوقيع دون اللاحقين المضمونين من طرفه In addition to the external solidarity which binds the signatories of the commercial paper with the holder, the legislator has established a form of internal solidarity between the signatories between them, so that the law allows each site having paid the value of this paper to return to the different signatories individually or collectively with all that they have accomplished without incurring a certain share and enjoying all the rights. Coming out of this paper from which the previous holder benefited, however, this return made by the taxpayer only concerns the guarantors who preceded him in the signature without the following guarantees by him.
Keywords: Committed exchange; External solidarity; Internal solidarity; Morphological return; Morphological solidarity; التضامن الخارجي; التضامن الصرفي; الرجوع الصرفي; الملتزمين الصرفيين

The Impact of Covid-19 Pandemic on Women In Nigeria - Iheanacho-Shahid, Jennifer (African Journal of Politics and Administrative Studies, 2021)
The paper examines the impact of corona-virus pandemic on women in Nigeria. Emergencies and times of unrest have been linked with increasing reports of Gender Based Violence. Pandemics and Epidemics on the other hand are no exception. The COVID-19 pandemic has been associated with an increase in Gender Based Violence termed the Shadow Pandemic due to the control measures adopted in containing the spread of the virus. The paper adopted the Social Ecological Model to explain and understand the factors that contribute to the increase of Gender Based Violence against women during emergencies or natural disasters and how interaction of individual and environmental factors influence behavior and attitudes that create an atmosphere that encourages violence. The paper was based on secondary sources of data.  The findings of the paper revealed that the lockdown isolated women and attenuated opportunities for them to divulge the abuse or receive necessary support services or resources.  The paper also discovered that there has been an increased rate of reported cases of Gender Based Violence during the months of lockdown in Nigeria. The paper concluded that the corona-virus outbreak has exposed the shadow pandemic of violence and inequality and the exclusion of the Minister of Women Affairs and Social Development is a step in the wrong direction . The paper recommended that it is pertinent to integrate gender lens into disease response and protection mechanism and Gender Based Violence services should be termed as essential duties during crisis and emergencies.

Mondialisation et harmonisation : vers l’émergence d’un cadre normatif à caractère régional des affaires Africain. Cas Maroc-OHADA - Rabhi, Tauofik (Annales de l’Université d’Alger, 2021)
Partant du constat que le droit est un phénomène social, l’harmonisation des législations apparaît indispensable au développement de zones économiques d’échange comme le sont la Communauté européenne et l'Accord de libre-échange nord-américain. Harmoniser, c’est dégager des directions et des orientations communes, établir des principes et des règles de base communs. En effet, dans un contexte de mondialisation et de globalisation il s’est opérées de grandes mutations économiques contemporaines modifiant ainsi les conditions du développement de certains pays africains, incitant désormais un mouvement d’intégration juridique en fonction des facteurs économiques, politiques, sociaux voire stratégique. Sur le plan économique, il y un rapprochement juridique visant l’harmonisation des législations et une intégration juridique qui s’est manifestée par une ouverture vers l’extérieur adoptant une politique de libéralisme économique. Le Maroc, de part son positionnement géographique a exprimé son désir de faire partie de ce rapprochement juridique on exprimant sa volonté à adhérer à l’OHADA.

Réflexions sur la pertinence du rejet de la théorie de l’universalisme du droit des obligations - Badji, Patrice Samuel Aristide (Revue d’étude et de recherche sur le droit et l’administration dans les pays d’Afrique, 2021)
Saleilles, subjugué par la codification allemande, croyait en l’existence d’un droit applicable partout, en tout temps et en tout lieu. Cette représentation est-elle une réalité concernant le droit des obligations, épine dorsale du droit privé ? La position de certains auteurs est claire : l’universalisme du droit des obligations est un mythe pour au moins deux raisons : rupture du droit français d’avec le droit romain et existence d’un lien entre régime politique et économique et régime juridique. Cependant, le constat que l’on peut faire est que les arguments invoqués au soutien du rejet de la théorie de l’universalisme du droit des obligations sont cantonnés ou peu approfondis, pour une question aussi importante. Notre étude se propose modestement de dépasser cette posture. En effet, de façon concrète, là où le système de la common law, en matière de faute est basé sur la casuistique, tel n’est pas le cas en droit français où celle-ci est appréciée de façon abstraite. Les exemples de la divergence entre ces deux systèmes peuvent être multipliés à souhait : fondements des devoirs précontractuels, privilège de la méthode objective d’interprétation du contrat, des dommages et intérêts punitifs, ignorance de la minimisation du dommage, rejet de la clause pénale, de la possibilité pour le juge de modifier le contrat devenu onéreux pour une partie au contrat. Au-delà, relevons qu’avec l’ordonnance du 10 février 2016, on note une distanciation du droit français, considéré jusqu’ici comme un modèle en matière législative, des pays africains, anciennes colonies. Enfin, la difficile gestation d’un Code civil européen et d’un Acte uniforme OHADA des contrats, conforte à suffisance les raisons du rejet de la théorie de l’universalisme du droit des obligations.
Keywords: Code civil; Code civil européen; Contrat; Droit OHADA; Droit des obligations; Effectivité; Représentation; Responsabilité; Système; Universalisme

Le cautionnement notarié vivifié par la réforme des sûretés - Bourassin, Manuella (La semaine juridique. Notariale et immobilière, 2021)

Qualification et formation du cautionnement : une réforme en clair-obscur - Bourassin, Manuella (Revue des contrats, 2021)
Au regard des nouveaux textes issus de l'ordonnance du 15 septembre 2021 relatifs à la qualification du cautionnement, à son formalisme, à sa proportionnalité et à la mise en garde précontractuelle de la caution, une appréciation nuancée de la réforme s'impose. En effet, des clarifications, qui procèdent des précisions apportées aux critères de qualification du cautionnement, ainsi que de la suppression de règles de formation, légales ou prétoriennes, éminemment litigieuses, sont susceptibles de réduire les contestations du cautionnement et d'en renforcer l'efficacité. Cependant, l'ordonnance renferme aussi de nombreuses et diverses obscurités, ambiguïtés comme lacunes, qui risquent d'aviver le contentieux et de déjouer chacune des finalités de l'ordonnance.

La coexistence des juridictions supranationales OHADA et CEMAC en Afrique centrale : un potentiel conflit de compétence - Edzegue Mendame, Aristide (African Journal of Literature and Humanities, 2021)
Avec l’avènement des traités OHADA et CEMAC, deux niveaux de contrôle juridictionnel des normes communautaires existent désormais dans chaque Etat membre des deux organisations. Le premier contrôle juridictionnel s’exerce devant les juridictions nationales et le second devant les juridictions communautaires. Les violations du droit uniforme OHADA sont sanctionnées en premier lieu par les juges nationaux, à charge pour les parties d’exercer un recours devant les juges supranationaux. Dans l’un et l’autre cas, cette coexistence par superposition des organes juridictionnels nationaux et supranationaux rend nécessaire les recherches, dans leur conception, organisation, caractéristiques et fonctionnement, des critères de répartition des compétences entre les ordres juridictionnels nationaux et supranationaux d’une part et entre les ordres juridictionnels communautaires et uniformes d’autre part. With the advent of the OHADA and CEMAC treaties, two levels of judicial review of community standards now exist in each member state of the two organizations. The first judicial review is carried out before national courts and the second before Community courts. Violations of OHADA uniform law are sanctioned in the first place by national judges, on the condition that the parties seek recourse before the supranational judges. In both cases, this coexistence by superposition of national and supranational judicial bodies makes it necessary to research, in their conception, organization, characteristics and functioning, criteria for the distribution of competences between the national and supranational jurisdictional orders of on the one hand and between community and uniform jurisdictional orders on the other.
Keywords: CEMAC; Compétences; Intégration; OHADA; Supranationalité

Le contrat de commerce international, source contestable du droit - Koundé, Dédji (Revue Togolaise du Droit des Affaires et d'Arbitrage, 2021)
Une bonne partie de la doctrine juridique semble admettre le contrat de commerce international comme source du droit. Pourtant, plusieurs éléments pertinents intrinsèques et même extrinsèques au contrat de commerce international conduisent à contester sa qualité de source du droit. En effet, s’il est possible de retenir qu’il crée des normes, celles-ci sont en opposition avec les critères habituels et les spécificités de la loi. En recherchant des critères d’acceptabilité auprès de la jurisprudence, l’arrimage reste difficile notamment en raison de ce que les parties se tourneront souvent vers une juridiction arbitrale qui saura leur garantir la non-diffusion du litige et du contrat ; une recherche de confidentialité et de secret qui n’est pas de nature à susciter la naissance d’une force créatrice du droit. Le rôle d’influenceur de la doctrine s’en voit ainsi compromis puisqu’il faut que le contrat établi soit connu pour que la doctrine veuille, par son influence toucher le législateur à ce propos. Bref, dans l’ordre juridique interne, le contrat de commerce international, est contesté en tant que source du droit. La lex mercatoria ne semble pas non plus porter un meilleur écho à la thèse du contrat de commerce international comme source du droit. D’ailleurs, de nombreuses controverses remettent en cause sa qualité d’ordre juridique. Et si les pratiques contractuelles internationales organisées ou relativement spontanées sont d’une grande richesse inventive, elles ne semblent pas suffisantes pour alimenter une vraie théorie des sources mercatiques. La juridicité de la lex mercatoria étant contestée, il n’est possible d’y trouver une source du droit que dans l’hypothèse d’une juridicité propre à la lex mercatoria. Et l’émancipation de la lex mercatoria par rapport à l’ordre juridique national et international semble se confirmer.
Keywords: Commerce international; Contrat; Source contestable

Le préciput du légataire commerçant en droit béninois - Lassehin, Codjo Bienvenu (Le NEMRO : Revue trimestrielle de droit économique, 2021)
Le préciput du légataire commerçant consacre la suture entre le droit des régimes matrimoniaux et le droit des affaires. La réflexion sur le sort du préciput de cette figure de légataire rassure de la pertinence des interférences et introduit un nouvel horizon dans le droit de la famille. A l’évidence, le Code béninois des personnes et de la famille est resté embryonnaire. Il s’est pourtant enrichi de magnifiques apports issus des actes uniformes de l’OHADA sur le statut du commerçant et du Code civil avant l’entrée en vigueur du Code des personnes, qui font office de droit béninois. L’étude comporte un intérêt certain. Elle postule le déplacement du centre de gravité en militant pour la recherche et la maîtrise du sort du préciput grevant des biens affectés à l’activité commerciale dont il n’est pas surtout habituel de voir porter la qualité juridique de préciput. On en déduit un changement de paradigme qui porte à fixer les digues que les vagues des stipulations des contrats matrimoniaux ne peuvent franchir. Ce qui conduit à nuancer la thèse qui voit dans le préciput un instrument de contournement de la réserve héréditaire. Le sort du préciput du légataire commerçant est ainsi décidé par le droit des régimes matrimoniaux. En vertu de la nature commerciale et consomptible spécifique du préciput, à l’arrivée, le sort du préciput du légataire commerçant est limité dans sa constitution et discuté dans sa jouissance.

La souveraineté pénale des Etats dans une perspective évolutive du droit pénal - Levy, Koah Serge (International Multilingual Journal of Science and Technology, 2021)
La souveraineté pénale des Etats se présente comme une prérogative régalienne des autorités nationales, ceci dans le souci de garantir l’application stricte des règles juridiques internes. Les Etats sont jaloux de leur souveraineté pénale raison pour laquelle l’intégration juridique liée à ce domaine pénal est très complexe. Le traité révisé de la CEMAC a posé les jalons d’une intégration juridique pluridisciplinaire dans notre sous-région. C’est dans ce sens que plusieurs textes ont été adoptés au niveau communautaire, parmi lesquels le Règlement CEMAC de 2016 portant prévention et répression du blanchiment des capitaux et du financement du terrorisme et de la prolifération en Afrique centrale, ce règlement détermine et prévoit des sanctions pénales pour une catégorie d’infractions, et ces sanctions doivent s’appliquer directement aux Etats-membres de façon systématique. On assiste là à une révolution, une évolution significative dans le domaine de l’intégration juridique lié au volet pénal. Dorénavant, il est clairement indiqué que certaines incriminations ne relèvent plus du domaine de la souveraineté pénale nationale des Etats, mais relèvent plutôt des règles communautaires appliquées au domaine pénal et s’imposant au niveau interne. La conséquence logique de cette situation est que la souveraineté pénale des Etats reste indéniable face aux infractions pénales nationales, mais devient mitigée voire amoindrie en cas d’infractions pénales communautaires. The criminal sovereignty of states is a regalian prerogative of the national authorities, in order to guarantee the strict application of internal legal rules. States are jealous of their criminal sovereignty, which is why legal integration in this area is very complex. The revised CEMAC treaty has laid the foundations for multidisciplinary legal integration in our sub-region. It is in this sense that several texts have been adopted at the community level, including the 2016 CEMAC Regulation on the prevention and repression of money laundering and the financing of terrorism and proliferation in Central Africa, which determines and provides for criminal sanctions for a category of offences, and these sanctions must be applied directly to member states in a systematic manner. This is a revolution, a significant development in the field of legal integration in relation to criminal law. From now on, it is clearly indicated that certain incriminations no longer fall within the domain of the national criminal sovereignty of the States, but rather within the domain of Community rules applied to the criminal domain and imposed at the internal level. The logical consequence of this situation is that the criminal sovereignty of States remains undeniable in the case of national criminal offences, but becomes mitigated or even diminished in the case of Community criminal offences.
Keywords: Community criminal offences; Criminal law; Criminal sovereignty; Droit pénal; Infraction pénale communautaire; Infraction pénale nationale; National criminal offences; Souveraineté pénale

ضمانات الحماية المدنية للمستهلك في التعاقد الالكتروني - باهي, التركي; محمود, حياة (مجلة البحوث في الحقوق والعلوم السياسية, 2021)
ما بين القوة والضعف وجدت الحرية التعاقدية التي كان القانون هو المنقذ لها وهو ما تجسد في الاختيار الحر للمستهلك في العقد الالكتروني الذي تولد نتيجة تطور وسائل الاتصال عبر شبـــكة الانترنت، حيث تغـــيرت أنمـــاط الممــــارسات التجارية وأصبـحت عـقود الاستهــــلاك تتم عــــبر تقنيـــات الكترونية كالهاتــــف الفاكس البـــريد الالكتروني، ومواقع الويب بهدف الحصول على القبول من إيجاب تـلقاه المستهلك عبر إعلانات إلكترونية، و أمام هذا التطور أولت التـشريعات الوطنية والدولية الحديثة اهتماما بالغا بعقد الاســـتهلاك الالكتروني حيث عجزت النظرية العامة للعقد عن حمايــــته مما أدى إلى ظــهور منظومة تشريعية وقائية هدفها تجسيد هــذه الحماية في عقود الاستهلاك في البـيئة الالكترونية. Between strength and weakness, there is contractual freedom, so that the law is its savior and which is embodied in the free choice of the consumer in the electronic contract that was giving birth result by the development of means of communication over the Internet, where the patterns of commercial practices changed and consumption contracts became carried out through electronic technologies such as telephone, fax, e-mail, and web sites via broadcast Free, aiming to gain acceptance from an affidavit received by the consumer via electronic advertisements Faced with this development, national and international modern legislations have paid great attention to the electronic consumption contract, as the general theory of the contract failed to protect it, which led to the emergence of a preventive legislative system aimed at embodying this protection in consumption contracts in the electronic environment

La vulneración del derecho a la propiedad privada y seguridad jurídica con la declaratoria de utilidad pública o interés social con fines de expropiación - Ortiz, Jhon Alberto Granados; Cabrera, Enrique Pozo (Polo del Conocimiento, 2021)
El dominio es un derecho real que otorga al titular el uso, goce, y disposición de un bien, reconocido y garantizado en la Constitución de la República del Ecuador como un derecho fundamental entregado a la ciudadanía, que no es un derecho absoluto, puesto que el Estado tiene el poder limitarlo mediante la figura jurídica de la expropiación para satisfacer necesidades de orden público, previo un pago justo e indemnización. En este contexto, esta investigación ha buscado profundizar en la figura jurídica de la expropiación, en primera instancia en cuanto a la privación del bien inmueble y del derecho constituido a la propiedad privada; y en segunda instancia el impacto social generado al ciudadano al perder su propiedad, cuya orientación sobre la “valoración o avalúo” y el pago del “justo precio” limita acceder a una verdadera restitución del bien despojado. Se aplicó un tipo de investigación cualitativa, además de sustentar este esfuerzo académico con la utilización del método analítico – sintético, método histórico-comparativo e inductivo deductivo para esclarecer los fenómenos de esta figura, que han permitido definir lo que incide a vulnerar el derecho a la propiedad privada y seguridad jurídica en el diagnóstico para el cálculo del monto a pagarse por el bien inmueble afectado.
Keywords: Avaliação; Private property; Propiedad privada; Propriedade privada; Subsidio; Subsidy; Subvenção; Valoración; Valuation

Adoption des normes IFRS dans l’espace OHADA : Fondement théorique, intérêt et enjeux - Nyasseu, Emma Joachim; Yepdo, Florentin Gaël; Tatang Atabonfack, Pulchérie Léonie; Myskinole, Cheguem Shupo Davine (International Journal of Financial Accountability, Economics, Management, and Auditing, 2021)
Du fait des changements profonds qu’apportent les nouveaux concepts sur lesquels se base le référentiel de l’IASB, le passage aux normes IFRS a été qualifié d’une révolution comptable. Le but d’harmonisation de cette institution se réalise à travers la diffusion mondiale progressive des normes IFRS. Toutefois, les entreprises de la zone OHADA sont concernées par ce changement. Compte tenu de la rareté des travaux de recherche dans le domaine, nous essayons d’analyser à travers ce papier, l’adoption de telles normes en contexte OHADA. Pour y parvenir, cet article rappelle le mécanisme de passage aux normes IFRS dans l’espace OHADA, étudie ensuite l’intérêt pour les entreprises de cette zone et enfin met en évidence les enjeux liés à un tel projet. Les principaux résultats montrent que loin d’être un simple outil de présentation et de communication de l’information financière, les IFRS constituent pour les entreprises de la zone OHADA, un levier d’attraction des investisseurs et d’intégration économique.
Keywords: Normalisation comptable; Normes IFRS; OHADA; Référentiel; Révolution comptable

Sûretés exclusives : quelles limites ? - Bourassin, Manuella (Defrénois. La revue du notariat, 2021)
Dans l'ordonnance du 15 septembre 2021, la promotion des sûretés exclusives est flagrante et leur fragilisation est latente. Deux types de limites ressortent de la réforme : d'une part, l'exacerbation de conflits entre créanciers ; d'autre part, la soumission des sûretés comme exclusives à des règles communes.

Crise sanitaire et délais de procédure OHADA : peut-on écarter le droit uniforme pour appliquer une loi nationale ? - Kamgaing, Pierre-Claver (Revue du droit des affaires en Afrique, 2021)

Les mesures probatoires en matière de contrefaçon des droits de propriété industrielle dans le nouvel Accord de Bangui - Zéna Ngouné, Hugues Bérard (International Multilingual Journal of Science and Technology, 2021)
Dans l’Accord de Bangui (AB) du 24 février 1999, les mesures permettant d’apporter la preuve de la contrefaçon ressortent être des « parents pauvres ». Dans le sillage des réformes imposées par la mondialisation et la nécessité de renforcer les moyens de lutte contre la contrefaçon, l’Organisation Africaine de la Propriété Intellectuelle (OAPI) n’a pas manqué de réviser son dispositif législatif le 14 décembre 2015. Parmi les nouveautés contenues dans l’Accord de Bangui Révisé (ABR), il y a le renforcement des mesures probatoires. La saisie contrefaçon est maintenue et améliorée, tandis que les mesures aux frontières et des recherches d’informations sont nouvellement consacrées. Ces mesures tel que aménagées, vont davantage faciliter la preuve et la sanction du délit de contrefaçon. Mais pour une efficacité optimale, certaines clarifications relatives à leur mise en œuvre devraient être apportées. In the Bangui Agreement act of February 24, 1999, the measures allowing proof of counterfeiting to be overlooked. In the wake of the reforms imposed by globalization and the need to strengthen the means to fight against counterfeiting, the African intellectual property organization did not fail to revise its legislative instrument on December 14, 2015. Among the novelties contained in the Revised Bangui Agreement, there is the strengthening of proof measures. Counterfeit seizure is maintained and improved, while border measures and information searches are newly devoted. These measures as arranged, will further facilitate the proof and the sanction of offense of counterfeiting. But for optimal efficiency, certain clarifications relating to their implementation should be made.
Keywords: Accord de Bangui révisé; Contrefaçon; Mesures aux frontières; Propriété industrielle; Recherches d’informations; Saisie contrefaçon

Soft Law in International Investment Law and Arbitration - Adinolfi, Giovanna (The Italian Review of International and Comparative Law, 2021)
In the more recent decades, international investment law (“iil”) and arbitration have been going through a process of recalibration prompted by both the intensification of cross-border capital flows and the States’ growing concerns over the potential restraints iil may impose upon the pursuit of public interests. The present contribution will pay attention to a specific feature that can be observed within these developments, i.e. the role played by soft law in investment arbitration and, more generally, under iil, also with a view to assessing the impact on the formation of binding international law of instruments formally devoid of normative force within the international legal order. After an introduction (Section 1), the contribution is articulated into four sections. Section 2 will first define the field of investigation. The case law of investment tribunals and the treaty practice under the more recent iia s will be then explored as to the reliance on soft law instruments for the purposes of settling procedural (Section 3) and substantive issues (Section 4). Some final remarks will close (Section 5).

Les non-dits scabreux des réformes du système comptable normal de l'OHADA de 2017 - Mvogo, Jean (Revue Française d’Economie et de Gestion, 2021)
Les états financiers sont des documents de synthèse qui fournissent des informations importantes à l’entreprise pour la prise des décisions de gestion et aux organismes habiletés à utiliser ces informations pour d’autres analyses au niveau national et international. Ils sont constitués du bilan, du compte de résultat, du tableau des flux de trésorerie et des notes annexes pour le système normal de l’OHADA. Or, les dispositions de ces états financiers ne laissent pas déconcerter. Ainsi, nonobstant leur amélioration au cours des précédentes réformes, certaines limites se sont retrouvées encore dans ces états financiers, à l’opposé aux perspectives. Cet article analyse les conséquences que la suppression des charges immobilisées entrainerait chez les parties prenantes de l’entité. Il présente aussi le problème de référence qui concerne le compte 318, « marchandises hors activités ordinaires ». Il fustige enfin l’instabilité du troisième état financier de l’OHADA. Les suggestions suivantes sont donc effectuées : la réinstauration des charges immobilisées dans le bilan, le rattachement du compte 318, « marchandises hors activités ordinaires » à la référence BA et l’adoption des bases de stabilisation du troisième état financier du système normal de l’OHADA
Keywords: Charges immobilisées; Etats financiers; Instabilité; Référence; Suppression

Analyse du régime ambivalent de la saisie des rémunérations en droit de l’OHADA: Entre l’autorisation et l’interdiction - Mbokolo Elima, Edmond (International Journal of Innovation and Scientific Research, 2021)
Conservative foreclosures are those where measures are applied both as a precaution and as a means of pressure against the debtor. To this end, OHADA has therefore provided that in voluntary execution, any creator can, whatever the nature of his debt, force his defaulting debtor to perform his obligations to his follow-up or a precautionary measure to ensure the safeguard of his rights. This is the case for remunerations that can be entered following the prior conciliation procedure and not a direct entry. Les saisies conservatoires sont donc des mesures à la fois de précaution et à la fois des moyens de pression contre le débiteur. A cet effet, le législateur OHADA a donc prévu qu’à défaut d'exécution volontaire, tout créancier peut, quelle que soit la nature de sa créance, contraindre son débiteur défaillant à exécuter ses obligations à son égard ou pratiquer une mesure conservatoire pour assurer la sauvegarde de ses droits. C’est le cas des rémunérations qui peuvent être saisies suivant la procédure préalable de conciliation et non d’une saisie directe.
Keywords: Rémunération; Saisie conservatoire; Salaire

Les contraintes de l'application des injonctions en droit de la concurrence - Ekango Ekango, Emmanuel (International Multilingual Journal of Science and Technology, 2021)
L’injonction dans son sens général est un ordre du juge adressé à une partie au procès, de faire ou de s’abstenir de faire quelque chose. En droit de la concurrence, les autorités interviennent par l’injonction. La finalité corrective de cette sanction la diffère des amendes et des astreintes qui préviennent et répriment. En interdisant aux entreprises de faire quelque chose ou/et en leur imposant d’adopter un comportement, les autorités régulatrices interviennent autoritairement dans les relations contractuelles. Cependant, l’intervention dans le contrat pour des motifs de contrôle se trouve limitée. En effet, la protection du processus concurrentiel nécessite un contrôle des autorités régulatrices pour corriger les dysfonctionnements du marché. Mais, cet office des autorités n’inclut pas qu’elles se substituent à l’unité économique sanctionnée. Les autorités régulatrices se trouvent ainsi confrontées à la nécessité qu’il y a à préserver la liberté contractuelle. Elles sont contraintes par l’opposabilité de la liberté contractuelle et par les mesures liées à l’exécution forcée. The injunction in its general sense is an order of the judge addressed to a litigant, to make or to abstain from making something. In competition law, the authorities intervene by the injunction. The corrective purpose of this sanction makes it different from fines and periods that warn and repress. By forbidding the enterprises to make something and/or imposing them to adopt a behavior, the regulatory authorities intervene authoritatively in the contractual relations. However, intervention in the contract for the reasons of control is limited. Indeed, the protection of the competitive process requires a control of the regulatory authorities to correct the market failures. But, this function of the authorities doesn't include that they may substitute themselves for the punished economic unit. The regulatory authorities are confronted to the necessity of preserving the contractual freedom. They are forced by the opposability of the contractual freedom and by the measures bound to the forced execution.
Keywords: Autorité régulatrice; Contractual freedom; Corrective purpose; Dysfonctionnement du marché; Exécution forcée; Finalité corrective; Forced execution; Injonction; Injunction; Liberté contractuelle; Market failures; Opposability; Opposabilité; Regulatory authority

La protection des données personnelles du cyberconsommateur par le droit des technologies de l’information et de la communication de la CEMAC - Majilo Pombou, Linda Judith (International Multilingual Journal of Science and Technology, 2021)
La multiplication des activités électroniques au sein des États membres de la CEMAC a favorisé l’institution d’une autorité de régulation dont l’une des plus prestigieuses missions est la protection des droits des consommateurs. En effet, Les questions relatives à la protection des données personnelles à l’ère du numérique occupent désormais une place importante dans le droit des activités économiques au sein de la CEMAC. L’environnement juridique des affaires de la CEMAC s’est alors acclimaté pour encadrer les réalités juridiques liées aux activités économiques dématérialisées. Si la volonté du législateur communautaire de faire des techniques de communication électroniques un socle du développement est visible à travers l’institution d’un marché numérique dans lequel prime la protection des droits et la liberté des consommateurs, il faut encore relever sa hardiesse à travailler pour la sauvegarde de l’économie numérique par des règles qui protègent les données personnelles des consommateurs des services électroniques. Ces règles protectrices ont été définies par le législateur dans le but d’amoindrir les risques que l’informatisation pouvait faire courir à la vie privée et aux données à caractère personnel du consommateur. Ainsi, un ensemble de principes devant encadrer le traitement des données à caractère personnel a été consacré. Ces principes confèrent au consommateur certains droits. Le droit de la CEMAC concernant les technologies de l’information et de la communication témoigne ainsi sa volonté de protéger les usagers des technologies du numérique. The proliferation of electronic activities within CEMAC member states has encouraged the establishment of a regulatory authority, one of whose most prestigious missions is the protection of consumer rights. Indeed, questions relating to the protection of personal data in the digital age now occupy an important place in the law of economic activities within CEMAC. CEMAC's legal business environment was then acclimatized to frame the legal realities related to dematerialized economic activities. We still need to raise the freedom to work hard to safeguard the digital economy through rules that protect the personal data of consumers of electronic services. These protective rules have been defined by respecting the personal character of the consumer. Thus, a set of principles that should govern the processing of personal data has been established. These principles give the consumer certain rights. CEMAC's law relating to information and communication technologies thus testifies to its desire to protect users of digital technologies.
Keywords: CEMAC; Consommateur; Consumer; Données personnelles; Personal data; Protection

Pratique de l'arbitrage international en Algérie : enjeux et modernisation - Bouchelaghem, Saloua (Revue des Sciences Juridiques et Politiques, 2021)
A l’instar des autres pays, l’Algérie a adopté la conception dualiste de l’arbitrage, avec un régime juridique réservé à l’arbitrage interne et un autre destiné à réglementer l’arbitrage international par des dispositions particulières (Titre II Chapitre IV du CPCA). Ce qui laisse supposer une plus grande faveur pour l’arbitrage international dont le régime juridique est moins contraignante que celui de l’arbitrage interne. Ce droit de l’arbitrage parvenu certes à un stade en évolution vers la modernité ne comporte pas moins certaines lacunes que le législateur ne manquera pas de combler au gré de l’expérience de la pratique. Like the other countries, Algeria has adopted the dualistic conception of arbitration, with a legal regime reserved for internal arbitration and another intended to regulate international arbitration by specific provisions (Title II Chapter IV of the CPCA). This suggests a greater favor for international arbitration, whose legal regime is less restrictive than that of internal arbitration. this law of arbitration, which has certainly reached a stage in evolution towards modernity, nevertheless has certain shortcomings, which the legislator will not fail to fill with the experience of practice.
Keywords: Algérie; Arbitrage; Arbitrage international; Arbitragem; Arbitraje; Arbitration; Contrôle des sentences internationales; Etat; Examination of international awards; Juge étatique; Personnes publiques; State judge; public figures

L’établissement de la filiation naturelle post mortem en droit camerounais - Pinlap Mbom, Willy Claudel (International Multilingual Journal of Science and Technology, 2021)
Après la mort, la personnalité juridique s’éteint. Le corps du défunt est, lui, toujours présent. N’étant plus le support d’une personne juridique, le cadavre est désormais une chose, mais une chose spécialement protégée, une chose sacrée. Retenir une telle qualification ne revient cependant pas à nier sa qualité de personne humaine digne de respect. Au nom de la dignité humaine, le respect de la dépouille mortelle se voit assuré par le droit pénal qui incrimine toute atteinte à l’intégrité physique du cadavre. L’intégrité physique du cadavre doit donc être préservée, dans le même temps, la filiation des vivants doit pouvoir être établie. Il en résulte un conflit d’intérêt : préserver la paix des morts versus faciliter l’établissement de la filiation des vivants ; d’où la question de savoir si la mort peut constituer un obstacle à l’établissement du lien de filiation. Si dans certaines situations elle n’en constitue pas un, il reste que dans d’autres, la mort de l’enfant ou du parent selon le cas peut constituer une difficulté, voire une barrière à l’établissement du lien. Toute chose qui ne concourt nullement à la protection des intérêts des vivants et plus spécialement de l’intérêt supérieur de l’enfant, acteur majeur du droit de la filiation. S’impose alors la nécessité de corriger les écueils de la législation camerounaise en la matière pour un droit de la filiation toujours plus conforme à l’intérêt de l’enfant.
Keywords: Birth; Enfant sans vie; Etat des personnes; Filiation; Legal personality; Lifeless child; Mort; Naissance; Personnalité juridique; State of persons

Capacity of the International Investment Arbitration Mechanism in Environmental Protection - Habibi Majandeh, Mohammad; Gholami, Afife (Public Law Researsh, 2021)
Environmental considerations have always been a challenge for foreign investment. The need to observe environmental minimums from the beginning to the end of the investment is also a concern of environmental law activists. In the meantime, the host state faces sometimes conflicting commitments. State dual obligations to foreign investors on the one hand, and the whole citizens on the other, has in many cases led to disputes, rooted in environmental norms. The main question is how the arbitration mechanism can take an active stand in the face of such disputes? The main purpose of this study is to examine the reflection of these conflicts in investment arbitration and the importance and role of arbitration in improving the environmental status. The authors of this paper believe that the arbitration system has tools that it can use in resolving disputes to balance these conflicting obligations. Some of these legal tools are directly or indirectly related to investment agreements, and others are beyond the treaty and based on international principles, rules, customs and practices. ملاحظات محیط زیستی همواره یکی از چالش های پیشروی سرمایه گذاری خارجی بوده است. لزوم رعایت حداقل های زیست‌محیطی از آغاز تا پایان سرمایه گذاری، از دغدغه های فعالان حوزه حقوق محیط زیست نیز می باشد. در این میان دولت میزبان با تعهداتی بعضاً متعارض روبروست. تعهدات دوگانه دولت در برابر سرمایه گذار از یک طرف و عموم شهروندان از طرف دیگر، در موارد متعددی به بروز اختلافاتی منجر شده که ریشه در هنجارهای محیط زیستی دارد. پرسش اصلی این است که سازوکار داوری در مواجهه با این نوع اختلافات، چگونه می تواند فعالانه موضع گیری نمایند؟ هدف اصلی این مطالعه بررسی بازتاب تعارض ها در رویه داوری سرمایه گذاری و اهمیت و نقش داوری در بهبود وضعیت محیط زیستی است. نویسندگان این نوشتار بر این باورند که سیستم داوری، ابزارهایی در اختیار دارد که می تواند از آنها در جریان حل اختلاف برای ایجاد تعادل میان این تعهدات متعارض استفاده کند. برخی از این ابزارهای حقوقی مستقیم یا غیرمستقیم با معاهدات سرمایه‌گذاری مرتبط است و دستهای دیگر فرامعاهده ای و ناشی از اصول، قواعد، عرف ها و رویه های بین المللی است.
Keywords: Arbitrage; Arbitragem; Arbitration; Bilateral Treaties; Environmental Protection; International Arbitration; Investment Disputes; Legal Instruments; ابزار حقوقی; اختلافات سرمایه‌گذاری; حمایت از محیط ‌زیست; داوری بین‌المللی; معاهدات دوجانبه

Caractéristiques de l’organisation comptable et qualité de l’information comptable et financière produite par les PME : le cas du Cameroun - Ngongang, Dagobert; Ngoe Mekando, Alex Cyrille (Revue Economie, Gestion et Société, 2021)
The purpose of this study is to analyze the impact of the characteristics of the accounting organization on the quality of the accounting and financial information produced by SMEs. A binary logistic regression analysis, a simple linear regression and a chi-square test on the data collected by administering a questionnaire from a sample of 73 SMEs constituted by reasoned choice allow, on the one hand, to observe that the SMEs Cameroonians are setting up an accounting organization in order to produce not only mandatory accounting information, but also accounting information intended for their own use. On the other hand, the empirical conclusions of this study show that the use of a service provider in the context of an outsourcing of the accounting function and the degree of computerization of the accounting activity positively and significantly influence the quality of accounting production. and finance for SMEs. Conversely, the feminization of the accounting function is found to be one of the characteristics of the accounting organization without influencing the quality of the accounting and financial product of SMEs.
Keywords: Accounting organization; Degree of computerization; Degré d’informatisation; Externalisation; Feminization; Féminisation; Organisation comptable; Outsourcing; Quality; Qualité

Comparison of Egyptian and English Mediation Procedures in Construction - Swelam, Ahmed; Eldosouky, Adel Ibrahim; El Korany, Tamer Mostafa (Journal of Engineering Research, 2021)
The mediation process is the parties' will to the dispute to reach an amicable, non-binding settlement to end their dispute. The Egyptian legislature adopted the idea of issuing a draft law on mediation in civil and commercial matters to settle disputes between the parties, whether before the litigation stage or after appearing before the courts. The Egyptian Ministry of Justice held many community dialogue sessions to find the final version of the draft law. However, the concerned authorities have not issued the law until writing this paper. This research aims to compare and analyze the Egyptian mediation procedures and the British mediation procedures to improve, develop, and enhance the Egyptian ones especially the draft law as well as overcoming the obstacles that hinder the spread of mediation. On the one hand, presenting the Egyptian procedures in the draft mediation law and the rules of the Cairo Regional Center for International Commercial Arbitration, CRCICA. On the other hand, the British procedures represented in the Institute of Civil Engineers' mediation rules, ICE.
Keywords: Egypt; England; Mediation

La comptabilité de l'OHADA face au choix des spécificités des activités économiques - Mvogo, Jean (Revue Internationale des Sciences de Gestion, 2021)
La prédominance des comptes spécifiques de l’activé commerciale, industrielle et agricole dans le plan des comptes de l’OHADA au détriment d’autres activités, accule de scruter les particularités de celles-ci. Car, la portée sociale et économique des autres activités telles que l’activité hôtelière, l’activité associative, l’activité d’enseignement…, nécessite déjà une attention particulière sur le plan comptable. La portée d’un tel exercice a pour objectif non seulement de répertorier les spécificités comptables des activités commerciales, industrielles et agricoles mais aussi et surtout de proposer les particularités des autres activités à forte demande d’intégration dans le plan des comptes de l’OHADA. En premier lieu, cet article montre, classe par classe, les différents comptes qui permettent d’entrevoir les spécificités comptables de l’activité commerciale, industrielle et agricole. En second lieu, l’étude observe des limites sur le principe de parallélisme et de correspondance comptable sur les comptes de l’activité agricole et du compte marchandises hors activités ordinaires, et trouve donc un intérêt certain dans l’appel à l’insertion des comptes spécifiques des autres activités importantes ayant des particularités établies à défaut de créer des plans de comptes spécifiques.
Keywords: Comptabilité; OHADA; Plan comptable; Plan des comptes; Spécificités comptables

L’action privée contre les pratiques anticoncurrentielles en Zone CEMAC - Baran, Doris Aimée (International Multilingual Journal of Science and Technology, 2021)
La volonté des consommateurs à faire valoir leurs droits face à un professionnel n’est pas dans la pratique une évidence. Ils sont confrontés à des entraves tant psychologiques qu’économiques qui les empêchent d’estimer avec raison tous les enjeux que cela représente pour eux. Il convient tout d’abord de relever que la matière juridique ainsi que l’accès à la justice en elle-même ne sont pas forcément leur apanage. Ils ne sont pas toujours les mieux outillés face aux litiges, notamment ceux ayant trait au domaine dans lequel ils ont vocation à agir, c’est-à-dire la consommation de biens et de services. Comment pourrait-il en être autrement, dans le cadre du droit de la concurrence, sphère caractérisée par sa technicité et ses conceptions parfois inaccessible sur le plan intellectuel ? Ajouté à cela, il se retrouve confronté à des difficultés financières, une action pouvant engendrer des frais au-dessus du profit qui aurait été éventuellement produit, ce qui ne suscite guère l’enthousiasme des consommateurs. Cette conséquence contribue aux faiblesses du « private enforcement ». Un dernier aspect, tient au fait que le domaine concurrentiel est particulier, et les consommateurs ne perçoivent pas toujours le contenu de leur préjudice. La mise en œuvre de l’action collective semble malaisée concernant les infractions anticoncurrentielles, les victimes étant généralement en grand nombre, pour un préjudice diffus, et pour laquelle l’exigence d’un mandat de chaque consommateur est une règle bien trop contraignante. La situation inhérente au consommateur, et les carences des moyens d’agir, explique le peu d’intérêt des consommateurs.
Keywords: Class actions; Competencia; Competition law; Competitive offenses; Concurrence (droit); Consommateur; Consumer; Damage; Dommage; Infractions concurrentielles; Private enforcement; Recours collectifs

L’efficacité du transfert fiduciaire d'une somme d'argent à titre de garantie en droit OHADA - Doungmegne Tadzong, Dorothée (International Multilingual Journal of Science and Technology, 2021)
Le transfert fiduciaire d’une somme d’argent à titre de garantie a été introduit en droit OHADA à l’occasion de la réforme de l’Acte uniforme sur le droit des sûretés en 2010. S’interroger sur l’efficacité de cette sûreté revient à affirmer qu’elle lui fait défaut. En cas de défaillance du débiteur en situation normale, le bénéficiaire est protégé partiellement. Les fonds donnés en garantie sont inscrits sur un compte bloqué, ouvert au nom du créancier de cette obligation, dans les livres d’un établissement de crédit habilité à les recevoir. Cependant, le législateur prévoit bien un transfert de propriété de ces fonds, mais reste muet sur l’identité du bénéficiaire du transfert. Il ne précise pas non plus si la mention du « compte bloqué » sur lequel les fonds doivent être versés signifie que ceux-ci sont détenus dans un patrimoine fiduciaire séparé du patrimoine de la banque. Cette imprécision impacte sur l’efficacité de la garantie en cas de défaillance du constituant soumis à l’ouverture d’une procédure collective de redressement judiciaire ou de liquidation des biens. Les atteintes sont alors portées aux droits du bénéficiaire, notamment à son droit de propriété et le droit de créance. The fiduciary transfer of a sum of money as a guarantee was introduced into OHADA law on the occasion of the reform of the Uniform Act on the law of securities in 2010. Questioning the effectiveness of this security is tantamount to asserting that he is lacking. In the event of default by the débtor in a normal situation, the beneficiary is partially protected. The funds given as collateral are entered in a blocked account, opened in the name of the creditor of this obligation, in the books of a credit institution authorised to receive them. However, the legislator does provide for a transfer of ownership of these funds, but remains silent on the identity of the beneficiary of the transfer. It also does not specify whether the mention of the « blocked account » into which the funds must be paid means that they are held in a trust patrimony separate from the patrimony of the bank. This imprecision has an impact on the effectiveness of the huarantee inthe event of default by the grantor subject to the opening of bankruptcy proceeding or liquidation of assets. The infringements are then brought to the rights of the beneficiairy, in particular to his right to property and the right of debt.
Keywords: Bankruptcy proceedings; Debtor; Debtor in good; Débiteur; Débiteur in bonis; Fiduciary transfer; Garantie; Money as collateral; Procédure collective; Transfert fiduciaire

La formation du concordat des petites entreprises en droit OHADA - Tinwo Fonkouo, Simplice Emmanuel (International Multilingual Journal of Science and Technology, 2021)
Le concordat est un instrument juridique mis sur pied par le législateur Ohada pour juguler les difficultés que les entreprises peuvent rencontrer au sein de cette espace économique. Il s’agit au sens des Actes Uniformes sur les Procédures Collectives et d’Apurement du Passif, des remises des dettes et des délais dont peut bénéficier le débiteur en vue de lui permettre le sauvetage de son entreprise en difficulté et l’apurement de son passif. La formation du concordat des petites entreprises renvoie à l’ensemble des règles juridiques applicables lors de sa conception. Il faut reconnaitre que les règles juridiques valables pour les grandes entreprises sont aussi pour les petites entreprises en droit Ohada. La formation du concordat est marquée par le respect de certaines exigences juridiques et une fois formé, il produit des effets. Ainsi, la formation du concordat nécessité les respects des exigences juridiques de droit commun et certaines exigences spécifiques. La prise en compte du consentement, la licéité, de la capacité des parties et l’objet certains est nécessaire au cours de cette formation. Il faut également noter que le respect de certaines exigences de fond et celles relatives à l’acte du concordat n’est pas négligeable. Sa formation conduit nécessairement à un impact à l’égard des parties et aussi à l’égard des tiers. The Concordat is a legal instrument set up by the Ohada legislator to curb the difficulties that companies may encounter within this economic space. Within the meaning of the Uniform Acts on Collective and Liability Clearance Procedures, this refers to the remission of debts and the deadlines from which the debtor may benefit in order to allow the rescue of his company in difficulty and the settlement of its liabilities. The formation of the corporate debt arrangement refers to all the legal rules applicable when it was designed. It must be recognized that the legal rules valid for large companies are also for small companies. The formation of the concordat is marked by compliance with certain legal requirements and once formed, it produces effects. Thus, the formation of the concordat requires compliance with the legal requirements of common law and certain specific requirements. Taking into account the consent, the legality, the capacity of the parties and the certain object is necessary during this training. It should also be noted that compliance with certain substantive requirements and those relating to the act of the concordat is not negligible. Its formation necessarily leads to an impact with regard to the parties and also with regard to third parties.
Keywords: Concordat; Creditor; Créancier; Debtor; Droit OHADA; Débiteur; OHADA law; Petite entreprise; Small business

L’éclatement du cadre personnel de la transaction douanière au Cameroun - Yougouda, Hadidjatou (International Multilingual Journal of Science and Technology, 2021)
L’éclatement du cadre personnel de la transaction douanière est lié principalement au nombre excessif des structures intervenant dans le déclenchement de cette procédure. Ce cadre recouvre une pluralité des autorités publiques et des bénéficiaires qui rend de ce fait difficile le travail de leur classification. Force est de constater qu’au niveau des autorités publiques, les pouvoirs de ces dernières sont déterminés par rapport à leur grade et suivant l’importance des affaires traitées. Le pouvoir de transaction est par conséquent attribué restrictivement à des fonctionnaires désignés suivant une compétence hiérarchique établie en fonction de l’importance de l’affaire. Ces compétences sont actuellement réglées dans le cadre de la CEMAC par l’article 328 du code des douanes. S’il est vrai que la transaction doit être conclu par l’autorité administrative compétente, il arrive qu’elle soit conclue par un subordonné habilité à le faire. En ce sens, les textes prévoient fréquemment l’approbation de la transaction par l’autorité hiérarchique. Cette approbation est, selon les cas, la condition de l’engagement de la personne publique qui contracte ou la condition de l’application de la transaction. Ainsi, le déclenchement de la procédure transactionnelle relève, à titre principal, de la compétence des autorités nationales et communautaires, et, subsidiairement, de celle des services extérieurs et du ministère public. La situation est sensiblement plus complexe en ce qui concerne les bénéficiaires. Théoriquement, l’article 327 alinéa 1 du code des douanes CEMAC ouvre le recours à la transaction douanière à tous contrevenant qui la sollicite. Il est admis que cette expression vise aussi bien les auteurs que les complices ; les intéressés à la fraude, les civilement responsables, les cautions, les propriétaires des marchandises ou des moyens de transport dont la confiscation est encourue.

La création d’une activité commerciale conformément au droit OHADA et son application au TGI/Kindu - Elongo, Jean-Pierre Manga (International Journal of Innovation and Scientific Research, 2021)
The 1st and 2nd paragraph of Article 1 of the Uniform Act on General Trade Law states that Any trader, including any commercial corporation in which a state or other person of public law is associated, as well as any economic interest group, whose establishment or head office is located on the territory of one of the States Parties to the Treaty on the Harmonization of Business Law in Africa, as «States Parties», is subject to the provisions of this Uniform Act.OHADA law of developing common, simple, modern rules adapted to the reality of OHADA member countries. The one-stop shop for business creation is the mechanism for creating a business established in accordance with OHADA law. This mechanism is not yet being applied by the TGI/KINDU itself-if the Congolese legislator has already foreseen it.The registration of the register of commerce and real estate credit is carried out at the TGI/Kindu. The latter does not exercise the jurisdiction afforded by the aforementioned law pending the installation of the single business start-up window in Kindu. However, the provisions of Article 17 which stipulate that the application for business creation is made by a single form filled out, signed and filed at the Single Box Office by the applicant, a natural or legal person, in this case a TGI/Kindu registry would be filed, which serves in the event that the one-stop shop for business creation is not yet effective.Commercial and cooperative companies that go to the registry for registration do not even file company deeds or statutes with the registry of the TGI / Kindu. Yet this is a legal requirement.
Keywords: Activité commerciale; Droit commercial; Kindu; TGI

Post award arbitral tribunal's mandate under the UNCITRAL Model Law and national laws based thereon - Al Hyari, Omar Hisham; Al Ani, Abdullah Rabee (Heliyon, 2021)
The UNCITRAL Model Law on International Commercial Arbitration provides for the extension of the mandate of the arbitral tribunal post issuance of the final award for the issuance of correction, interpretation, additional award, and remittance of the award back to the arbitral tribunal to remove grounds for challenging the award. Using a doctrinal approach, this paper examines the deviations of the national laws of adopting jurisdictions from the Model Law in regards to this extended mandate, and evaluates the improvements and drawbacks in these deviations. Mainly, the findings of this paper are that, of the many deviations, the positive changes are those that provide comfortable and lenient default provisions for the benefit of inexperienced parties, and since correction, interpretation, additional award, and remittance are useful provisions that are designed to help self-rectify the arbitral process, without adversely delaying it, then the changes that increase the efficacy of these provisions are welcomed. On the other hand, unnecessary deviations are seen as drawbacks that hinder the harmonization of national arbitration laws aimed at by the Model Law. The adopting jurisdictions shall be limited to those acknowledged as such by the UNCITRAL.
Keywords: Additional award; Arbitrage; Arbitragem; Arbitration; Arbitrators' mandate; Award; Correction; Interpretation; Model Law jurisdictions; UNCITRAL Model Law

Mediación y Cultura de Paz en los Objetivos de Desarrollo Sostenible 2030 - Gonzalo-Quiroga, Marta (Polo del Conocimiento, 2021)
El objetivo de la presente contribución es analizar el papel de la mediación como bisagra referencial entre dos de los Objetivos de Desarrollo Sostenible (ODS) para 2030: el núm. 4 -Educación- y el núm. 16 -Paz, Justicia, e Instituciones sólidas-. La metodología empleada parte de un estudio del panorama internacional para detenerse en la legislación española, tanto en mediación como en educación en cultura de paz, con las correspondientes novedades al respecto. Todo ello responde a una investigación analítica sobre distintas bases legislativas, documentales y bibliográficas que, como resultado, ha dado lugar a la creación de distintas tablas que resumen la investigación y, pretendemos, contribuyan a facilitar su difusión, en el marco de los ODS 2030. Se trata así de promover la mediación como una de las herramientas esenciales para fomentar la convivencia pacífica, la educación y la justicia en el contexto universal de la cultura de la paz.
Keywords: Cultura de Paz; Cultura de paz; Culture of Peace; Educación; Education; Educação; Justice; Justicia; Justiça; Mediación; Mediation; Mediação; Objetivos de Desarrollo Sostenible (ODS); Objetivos de Desenvolvimento Sustentável; Sustainable Development Goals

Repenser les acteurs de la vente commerciale OHADA - Ahmadou, Mohamadou (International Multilingual Journal of Science and Technology, 2021)

Le contrat déséquilibré par l'imprévision à l'aune de l'avant-projet de texte uniforme portant droit général des obligations - Badawe Kalniga, Dieu Ne Dort (International Multilingual Journal of Science and Technology, 2021)
Le sort du contrat déséquilibré par l’imprévision a évolué avec l’avènement de l’Avant-projet de texte uniforme portant droit général des obligations. Cet instrument juridique prévoit à la suite des législations anationales et certaines législations nationales la révision du contrat pour imprévision. Dans ce mécanisme de gestion de l’imprévision, les parties au contrat ont une place préférentielle. Ce n’est qu’en cas d’échec d’une gestion amiable de l’imprévision que le juge est habilité à intervenir. The fate of a contract unbalanced by unforseen circumstances has evolved with the advent of preliminary draft uniform text on general law of obligations. This legal instrument provides, following international laws and certain national laws, for the revision of the contract for unforseen circumstances. In this unforseen management mechanism, the parties to the contract have a preferential place. It is only in the event of failure of an amicable management that the judge is authorized to intervene.
Keywords: Avant-projet de texte uniforme; Contract; Contracting parties; Contrat; Droit général des obligations; General law obligations; Hardship; Imprévision; Judge; Juge; Parties; Preliminary draft of uniform text

La protection juridique de la femme en droit tchadien : entre réalités et incertitudes - Dar, Didegomi (International Multilingual Journal of Science and Technology, 2021)

Réflexion à propos de la place du juge dans la procédure préventive consensuelle en droit OHADA des entreprises en difficulté - Guidakre, Bamanga Daga (International Multilingual Journal of Science and Technology, 2021)
Le juge, qui, autrefois était étranger à la matière contractuelle, se trouve aujourd’hui associé à la procédure préventive consensuelle que représente la conciliation. Le législateur OHADA semble avoir posé par cette innovation majeure un principe qui bousculerait à coup sûr les règles classiques du droit des contrats qui préconisaient la non-immixtion du juge dans les contrats. Cette rupture de la tradition juridique dans l’AUPC rénové trouve ainsi son socle dans le souci de sacraliser le pouvoir du juge dans la validation de l’accord des parties et son exécution. Aussi, on peut percevoir dans ces missions du juge un rôle d’examination ou de régulation. The judge, who once was foreign to contractual matters, is now involved in the consensual preventive procedure that conciliation represents. The OHADA legislator seems to have established by this major innovation a principle which would undoubtedly shake up the classic rules of contract law which advocated the non-interference of the judge in contracts. This break in the legal tradition in the renovated AUPC thus finds its basis in the concern to sanctify the power of the judge in the validation of the agreement of the parties and its execution. Also, we can perceive in these missions of the judge a role of examination and regulation.
Keywords: Consensual preventive procedure; Judge; Juge; Procédure préventive consensuelle

L’existence du contrat de travail : une nécessité pour procéder à la rupture de la relation de travail en droit camerounais ? contribution à la lumière du droit comparé - Mvondo Eleme, Mireille Angeline (International Multilingual Journal of Science and Technology, 2021)
Il est récurrent dans la pratique qu’en présence d’un différend de travail entre les parties, l’on se rende compte au moment de rompre la relation de travail en cause, que celle-ci est dépourvue d’assise juridique. En effet, les contrats verbaux n'étant valables que pour des formes restreintes de relation de travail que sont les relations précaires, c’est le plus souvent, par négligence, qu’on constate, à l’instant de la rupture d’une relation de travail donnée, que celle-ci n’avait pas véritablement de fondement juridique à l’instar d’un contrat de travail. En pareilles circonstances, comment reconnaitre l’effectivité d’une telle relation de travail afin de la rompre convenablement ? Cette préoccupation est primordiale dans la mesure où les droits attachés à la rupture d’une relation de travail diffèrent suivant la modalité de contrat sur laquelle elle repose ou si celui-ci n’existe même pas. Ainsi, à l’analyse, certains critères permettent de reconnaitre le type de relation de travail liant les parties, encore faut-il la prouver par des instruments fiables.
Keywords: Contrat de travail; Droit du travail; Labour law; Rupture

La preuve du cybercrime : les victimes à la traversée d'un labyrinthe - Nzoh Sangong, Job (International Multilingual Journal of Science and Technology, 2021)
Dans les cyber-relations, on côtoie le risque. On s’y cultive à l’anéantir, et on déploie aussi allégrement tous les moyens pour l’évincer. Or, le risque zéro dans les relations en général et dans le monde des affaires en particulier n’existe pas. Un tel postulat est renchéri dans les cyber-relations par la virtualité des échanges, l’absence des parties prenantes, la malléabilité des contenus, et partant, de l’incertitude de leurs identités réciproques. La notion de preuve est à cet effet importante, car elle préside à la sécurité des transactions. Sur Internet, la preuve des cybercrimes s’avère complexe au regard des possibilités matérielles et techniques lui permettant d’usurper des identités, voire de se travestir d’une part et de manipuler, falsifier et crypter les documents et contenus numériques. Ainsi, au-delà de l’identification et de la production des preuves qui sont un préalable de sécurité juridique des transactions, il parait crucial de relever qu’il s’en dégage une interrogation jusque-là inédite celle de la pertinence des preuves des cybercrimes ? Cela étant, prouver le cybercrime est une aporie processuelle pour les victimes internautes et pour les autorités judiciaires. En effet, la conduite d’un procès pénal relatif à la cybercriminalité expose la victime et le ministère public à deux principaux écueils : l’identification du cybercriminel et la preuve de son infraction. Il en résulte une complexité de l’identification du cybercriminel d’une part et une instabilité des documents et contenus cybercriminels d’autre part.
Keywords: Arnaque; Cybercriminalité; Cybercriminel; Cybersécurité; Identité; Internaute; Preuve; Victime

La classification diversifiée des créanciers dans les établissements de crédit en difficulté en zone CEMAC - Paydi, Raïssa (International Multilingual Journal of Science and Technology, 2021)
Nombreux sont les conflits d'intérêts à l'ouverture d'une procédure collective. Les créanciers sont les premiers à être intéressés par l'insolvabilité du débiteur lors d'une telle procédure. C'est pour cela que le législateur a opéré une classification des différents types de créanciers fondée sur le principe de l'égalité car, le premier droit octroyé à tout créancier est la prise en compte de sa créance dans le cadre d'une procédure collective. La consécration des droits et devoirs égalitaires des créanciers est une réalité, il constitue une protection accordée à tous les créanciers. Mais ce principe n'est pas sans exception car, tous les créanciers ne sont pas égaux, mais certains créanciers sont plus égaux que d'autres. A cet effet, pour rétablir l'équilibre il sera primordial d'accorder des privilèges à certains plus qu'à d'autres à cause, soit de la date de naissance de leurs créances ou à cause de la nature de leurs créances. Ainsi, les dispositions sur la classification des créanciers dans les sociétés de droit commun auront tendance à s'appliquer aux établissements de crédit en difficulté en zone CEMAC lors d'une procédure collective d'apurement de passif à cause de la passerelle juridique qui existe entre les deux ordres juridiques. There are many conflicts of interest when initiating bankruptcy proceedings. Creditors are the first to be interested in insolvency of the debtor in such a procedure. It's for that the legislator operated a classification of the different types of creditors based on the principle of the equality of creditors because the first right granted to any creditor is the taking into account of its claim in the context of bankruptcy proceedings. The consecration of rights and egalitarian duties of creditors is a reality; it constitutes a protection afforded to all creditors. But this principle is not without exception because, all creditors are not equal, but some creditors are more equal than others. To this end, to restore the balance it will be essential to grant privileges to some more than to others because of the date of origin of their claims. Thus, the provisions on the classification of creditors in common law companies will tend to apply to credit institutions in difficulty in the CEMAC zone during insolvency proceeding clearance of liabilities because of the legal bridge that exists between the two others legal.
Keywords: CEMAC; Creditors; Créanciers; Etablissements de crédit en difficulté; Troubled credit institutions

Reasonable awareness in compensation for infringement of IP rights - Vanbrabant, Bernard; Glorieux, Dietger (Revue de Droit Intellectuel. L'Ingenieur-Conseil, 2021)

Le système juridique unitaire à l’épreuve du droit coutumier : la nécessité d’une territorialisation du droit - Guémar, Carine (Studia Universitatis Babeș-Bolyai Studia Europaea, 2021)
The unitary legal system vs. customary law: the need of territorialization. The French State is a unitary State as opposed to federal States, in which there is one Constitution providing for provisions applicable throughout the territory of the French Republic. Unity can be found in a legal unity first, in this the unitary Law is the one that does not admit of territorial differenciation. A political and organic unity, since there is only one Parliament, one Government. A social unity eventually, which consists of the admission of a single French people. If the French tradition is based on a centralized system, the implementation of the process of territorial decentralization led to reconsider the uniformity of the Law precisely with the question of territorial differenciation and territorialisation of Law. The present study proposes to return to the consideration by unitary Law of local territories including the overseas territories with the problem of reconciling such a system with customary Law.
Keywords: Customary Law; Overseas territories; Territorial decentralization; Territorialisation of Law; Unitary Law

حكم عقـــد الزواج عبر وسائل الاتصـــال الحديثـــة - دشاش, راضية (مجلة مالك بن نبي للبحوث والدراسات, 2021)
يشهد العالم ثورة رقمية في جميع مجالات الحياة وحركة كبيرة في مجال المعلوماتية ، واستخدام تكنولوجيا الاتصال الحديثة لقدرتها الهائلة في تسهيل عملية نقل وإرسال المعلومات. حيث أصبح التعامل بهذه المخترعات في إبرام العقود المالية والتجارية وحتى الشخصية كعقد الزواج عبر وسائل الاتصال الحديثة الأمر الذي يتطلب نوعا من الحماية والثبات ذلك أن الكثير من الشباب قد يقعون ضحية نصب واحتيال جراء هذا الزواج الأمر الذي يدفع إلى التساؤل عن حكم الزواج عبر وسائل الاتصال الحديثة ؟ وفي حالة حصل ذلك ماهي أهم الوسائل التي يمكن للأطراف الاعتماد عليها لإثبات الزواج عبر وسائل الاتصال ؟ خاصة أنها مسألة مستجدة أصبحت تأثر على الأمن الأسري والاجتماعي وعليه فالقول بجواز الزواج عبر التقنيات المعاصرة لا يعني التوسع فيه وإنما يبقى اللجوء إليه في حالة ظروف لا تسمح للأفراد باللقاء، ومن ثمة تنبيه المشرع الجزائري لهذا الوضع الحساس من خلال النص على عقد الزواج عبر وسائل الاتصال الحديثة في قانون الأسرة وبيان طرق خاصة لإثباته تختلف عن غيرها . The world is witnessing a digital revolution in all areas of life as well as a great movement in the field of informatics, including the use of modern communication technology for its enormous ability to facilitate the process of transmitting and sending information. Dealing with these inventions leads to concluding financial, commercial and even personal contracts, such as the marriage contract through modern means of communication, which requires a kind of protection and stability. As a result, many young people may fall victim to deception, and this make marriage through modern means of communication in question. And if this happens, what are the most important means that the parties can rely on to prove the marriage through modern means of communication? Especially since it is an emerging issue that has affected family and social security, and accordingly, saying that marriage is permissible through contemporary technologies does not mean expanding it, but it remains to resort to it in the case of circumstances that do not allow individuals to meet. Hence, the Algerian legislator alerts this sensitive situation by stipulating the marriage contract through modern means of communication in Family law, showing special different ways to prove it.
Keywords: Communications modernes; Contract; Contrat de mariage; Contrats; Judgment; Jugement; Marriage contract; Modern means of communication; Reporter and electronic signature; Éditeur et signature électroniques; التعاقد; الحكم; المحرر والتوقيع الالكتروني; عقد الزواج; وسائل الاتصال الحديثة

Le juge fiscal camerounais : unité ou pluralité de juridictions ? - Fermose, Janvier (Les Annales de droit, 2021)
Le développement du contentieux fiscal moderne a conduit à un passage du dualisme juridictionnel à un pluralisme juridictionnel fiscal. S’il n’est pas évident d’avoir un juge unique qui statue sur l’ensemble de la matière fiscale, la préoccupation centrale est celle de savoir comment les juges fiscaux coexistent-ils dans l’ordre juridictionnel camerounais. Suivant l’hypothèse que cette coexistence est manifeste, l’étude privilégie l’analyse des textes juridiques et des décisions rendues par les juridictions fiscales camerounaises. D’une part, pour vérifier le bien-fondé de l’analyse, il ressort que, de par son identification, le juge fiscal camerounais est désormais un juge multiple, pluriel et diversifié : il est dual, en se référant au juge fiscal classique (administratif ou judiciaire), et spécial, si l’on fait allusion aux juges fiscaux constitutionnel, communautaire et régional. La diversité du juge fiscal permet alors d’observer que toutes les juridictions sont, à un titre plus ou moins, à compétences fiscales. Si pendant longtemps, le dualisme juridictionnel a été le socle institutionnel du contentieux fiscal, la notion de juge fiscal s’est aujourd’hui enrichie avec l’apparition des nouveaux juges fiscaux. D’autre part, comme corollaire, la pluralité des juges fiscaux pose le problème de leur cohabitation : l’on note une collaboration organique et fonctionnelle entre les juges intervenant en contentieux fiscal, mais cette coexistence n’est pas sans conséquence, car elle entraîne des incidences légales et jurisprudentielles.
Keywords: juge fiscal; juridiction; pluralité; unité

Les récentes réformes des finances sociales au Cameroun - Tekendo, Gaétan Siewe (Les Annales de droit, 2021)
Alerte sécu ! C’est par cette exclamation que l’on peut mettre en garde sur les potentielles menaces qui pèsent sur les finances sociales en Afrique en général et au Cameroun en particulier. Les régimes de sécurité sociale des pays d’Afrique noire francophone font face à de sérieuses difficultés financières. Ceux-ci éprouvent des difficultés à fournir à temps des prestations sociales aux travailleurs salariés et leurs familles. De prime abord, la mission d’une caisse de sécurité sociale est d...

La transmission universelle du patrimoine en droit des sociétés commerciales - Ahounang Kouanasse Épouse Nguekou, Nicole (International Multilingual Journal of Science and Technology, 2021)
Le législateur OHADA a prévu que la fusion, la scission et la dissolution de la société unipersonnelle personne morale entraine la transmission universelle du patrimoine aux sociétés avec pour conséquence l’acquisition par les sociétés qui disparaissent, de la qualité d’associés des sociétés bénéficiaires dans les conditions déterminées par le contrat de fusion en ce qui les concernent. Curieusement, il ne précise aucunement la quintessence ou du moins le contenu de la notion de « transmission universelle du patrimoine ».Or dire que les fusions – scissions et la dissolution impliquent transmission universelle de patrimoine mérite d’être éclairci compte tenu de la diversité et de la spécificité des contrats et des biens que regorgent une société. Cette clarification se justifie d’une part du fait que la transmission universelle est une notion issue du droit civil et plus précisément du droit successoral1 qui pour être appliqué au droit des sociétés commerciales mérite quelques précisions au vue des formalités qui ont cours dans ces sociétés en matière de transmission et de certains contrats dont la spécificité peut rendre complexe la transmission universelle du patrimoine.
Keywords: Contrats administratifs; Contrats en cours; Droit des sociétés commerciales; Intellectual property; Intuitu personae; Patrimoine; Propriedade intelectual; Propriété intellectuelle; Transmission universelle

Réflexions sur la production de la créance alimentaire dans l'acte uniforme portant organisation des procédures collectives d’apurement du passif à l'aune de la réforme de 2015 - Bella Noa, Gaëlle (International Multilingual Journal of Science and Technology, 2021)
Du fait de leur nature et de leur lien avec l’un des éléments essentiels de la vie et de la dignité de l’homme, les créances alimentaires ont toujours bénéficié d’un régime dérogatoire en droit. À leur service, des mesures de protection et d’exécution taillées sur mesure, dans toutes les matières, ou presque. En effet, le droit des procédures collectives de l’Organisation pour l’Harmonisation en Afrique du Droit des Affaires, par un silence assourdissant, faisait peu cas d’elles avant 2015. Sûrement parce que ses règles sont conçues pour les entreprises, et que ces dernières n’ont aucune obligation alimentaire à exécuter. C’était sans compter qu’au fil du temps, les procédures de concours ont été élargies aux personnes physiques, qui peuvent, elles, avoir des prestations alimentaires à fournir. Conscient de cela, le législateur de 2015 statue expressément sur leur sort. Il décide que les dettes alimentaires du débiteur in mali sont exonérées de l’obligation de production. Cette dispense produit des conséquences pas toujours aisées à cerner, d’où l’intérêt de mener quelques réflexions.
Keywords: Abstention; Conséquences; Créance alimentaire; Procédures collectives; Production

L’exigence de « compétence » dans le choix des administrateurs des sociétés anonymes avec Conseil d’Administration en droit OHADA des sociétés commerciales - Kouenguen Nguetnkam, Yannick (International Multilingual Journal of Science and Technology, 2021)
L’administration de la société anonyme est délicate. Elle exige la compétence pour les membres du conseil d’administration et spécialement des administrateurs. Ce papier se donne pour mission de s’interroger sur la prise en compte de cet élément dans leur sélection. Les résultats de la recherche démontrent que, la prise en compte de ce critère de compétence est mitigé voire tacite. On oscille entre silence et l’implicite. L’urgence d’inscrire expressément dans la loi uniforme OHADA la compétence comme critère par excellence du choix des administrateurs participe de la qualité du management, du contrôle et du rayonnement économique de la société anonyme. The management of anonymous societies is difficult. To do it, the members of administrators staff have to be competent. This paper have as aim to ask question and take in to consideration competence in the choice of administrators staff in the law. The result is competence is not take expressly. The proposition is, a legislator an obligation to insert in OHADA uniform law of society, the notion of competence like amazing sign to do the best choice of members of administrators staff. After it, we will have a quality management, a best control and economic grow of the anonymous societies.
Keywords: Administrateur; Board of directors; CEMAC; Compétence; Conseil d'administration; Corporate law; Directors; Droit des sociétés; Gouvernance; Governance; OHADA; Société Anonyme; Tacite

Les centres d’arbitrage de l’espace OHADA face aux technologies de l’information et de la communication (TIC) - Ndongo Dimouamoua, Céline (Revue Juridique de la Sorbonne, 2021)
Depuis l’adoption de l’Acte uniforme relatif au droit de l’arbitrage, les centres d’arbitrage se sont multipliés dans la zone OHADA. Même si tous ces centres ne sont pas au même niveau de développement, les acteurs économiques leur confient de plus en plus le règlement de leurs différends. Toutefois, la fermeture des aéroports, la limitation des déplacements, l’impossibilité de se réunir, conséquences de la crise sanitaire mondiale apparue en mars 2020, ont perturbé le fonctionnement des centres d’arbitrage du monde entier, y compris ceux situés dans la zone OHADA. En abolissant les distances et les contraintes de temps, les technologies de l’information et de la communication (TIC) se sont révélées être des moyens efficaces de contournement des difficultés nées de la pandémie. En effet, les grands centres d’arbitrage en ont profité pour mettre en œuvre des solutions technologiques permettant de réduire l’impact de la crise sur les procédures arbitrales. Dans cet environnement hautement concurrentiel, la question de l’arbitrage en ligne dans les centres d’arbitrage de l’espace OHADA s’est alors de facto posée. La question de la place réservée aux TIC dans l’administration des procédures par ces centres et les moyens d’y développer l’arbitrage à distance est posée. Pour répondre à cette double interrogation, un état des lieux de l’arbitrage en ligne dans les centres d’arbitrage de la zone a été fait. Il en ressort que les règlements d’arbitrage des centres abordent le sujet de manière lacunaire. Bien plus, l’environnement économique et technologique dans lequel ils évoluent peut constituer un frein au recours aux TIC. La nécessité de compléter les règlements d’arbitrage sur des questions comme la cybersécurité, l’organisation des réunions virtuelles ou encore la signature électronique des documents est clairement apparue. Afin d’accélérer le développement de l’arbitrage en ligne, les centres d’arbitrage situés dans l’espace OHADA doivent aussi former leur personnel à l’usage des TIC, encourager les parties à signer des cyber-protocoles, et mettre à leur disposition des guides d’usage des TIC dans les procédures arbitrales. En pratique, la révolution numérique dans les centres d’arbitrage africains n’aura pas lieu sans les efforts combinés des centres, des parties et des arbitres. 22 ans après l’adoption de l’AUA, la compétitivité et la maturité des centres d’arbitrage de l’espace OHADA seront fonction de leurs capacités à intégrer les TIC dans leurs méthodes de travail.
Keywords: Arbitrage en ligne; Arbitrage institutionnel; Arbitration centres; Centres d’arbitrage; Cyber protocol; Cyber-protocole; Guides sur l’arbitrage en ligne; ICT; Institutional arbitration; OHADA; Online Dispute Resolution; Online arbitration guides; TIC; Vidéoconférence

Les dettes du ménage et les droits des tiers - Yassi Tougou Keuni, Cédric (International Multilingual Journal of Science and Technology, 2021)
La décision de se retrouver dans un lien de mariage a des implications majeures sur le devenir des conjoints. Cette union qui est la matérialisation du couple, se traduit tant entre les personnes qu’entre leurs patrimoines. Dès la célébration du mariage, la nécessité de réguler efficacement l’association conjugale oblige la collaboration des époux avec les tiers fournisseurs de crédit ou de services de divers ordres. Ces rapports font naitre des dettes du ménage qui sont au cœur des relations entre les tiers et le couple. À l’épreuve du mariage, et dans le cadre du déroulement normal de la vie du couple, le tiers qui concourt à la gestion du foyer bénéficie d’une protection de ses droits à travers la solidarité des époux aux dettes du ménage. Même, quand le mariage doit prendre fin soit par la mort d’un conjoint, soit par le divorce, les droits des tiers par rapport aux dettes du ménage ne se trouvent pas conséquemment menacés. Ces droits persistent parfois jusqu’à impacter de façon particulière sur les héritiers.
Keywords: Dettes du ménage; Epoux; Household debts; Mariage; Marriage; Solidarity; Solidarité; Spouse; Third parties; Tiers

La publication des informations sociétales suivant les lois comptables revisées OHADA - Guimezap Épse Choukem, Claire (Revue Française d'Economie et de Gestion, 2021)
Dans un contexte marqué par le développement durable, le législateur OHADA n’a eu de cesse d’être accablé de toutes parts pour son statisme vis-à-vis de la montée des problématiques sociétales. Au lendemain des reformes du système comptable OHADA, les problématiques sociétales ont une fois de plus raté le rendez-vous de la normalisation. Toutefois, de nombreuses entreprises continuent à publier leurs informations sociétales parallèlement à leur communication financière. A cet effet, le problème que soulève cet article est celui de la compréhension des modes de production et de diffusion des informations extra-financières en l’absence d’une réglementation en la matière. Une étude empirique de nature descriptive est menée auprès d’un échantillon de 120 entreprises diffusant leurs informations sociétales au sein de l’espace OHADA. Il en ressort que le site internet et l’implication dans le développement de la communauté locale sont apparue respectivement comme support et thème de diffusion les plus utilisés dans l’espace OHADA en matière de reporting sociétal sous la pression de certaines parties prenantes notamment les associations consuméristes, les départements ministériels en charge de l’environnement, du travail et de la sécurité sociale. In a context marked by a widespread awareness of the needs of sustainable development, the OHADA legislator has been constantly burdened on all sides for its statism to the rise of societal problems. However, After the reform of the OHADA system, sustainability problems once more did not met up with the appointment of normalization. However, several enterprises continue to publish their societal information in parallel with their financial communication. As such, the problem raised by this article is that of understanding the mode of production and disclosure of non-financial information in the absence of a regulatory framework. A descriptive empirical analysis is carried out with a sample of 120 enterprises which propagate their societal information in the OHADA zone. It reveals that internet websites and implication in the development of the local community are respectively the medium and theme of the most used disclosures in the OHADA zone with regards to sustainability reporting under the pressure of some stakeholders especially consumer associations, ministerial departments in charge of the environment labor and social security.
Keywords: Accounting law; CSR; Corporate Social Responsibility; Droit comptable; Information sociétale; Parties-prenantes; RSE; Responsabilité Sociétale de l'Entreprise; Stakeholders

Règlement des litiges nés de la copropriété des immeubles en droit camerounais : réflexion sur une procédure « Janus » à la lumière de la loi N° 2010/022 du 21 décembre 2010 relative à la copropriété des immeubles - Kengne, Pascal (International Multilingual Journal of Science and Technology, 2021)

La portée de l'immatriculation dans la protection des commerçants en droit OHADA - Zoa Atangana, Jocelyne Gaëlle (International Multilingual Journal of Science and Technology, 2021)
L’efficacité de l’immatriculation dans la protection du commerçant est une réalité en droit OHADA. Elle se manifeste clairement à travers les différents avantages que procure l’immatriculation au commerçant. Une fois la formalité d’immatriculation accomplie, le commerçant va bénéficier des avantages que lui confère son statut tels que : le droit à la propriété commerciale qui implique automatiquement le droit au renouvellement du bail, le droit à la liberté de la preuve et le droit à une prescription plus courte. Contrairement au droit commun, les règles de droit commercial applicables au commerçant semblent être moins rigides. De même, qu’il s’agisse d’une personne physique ou d’une personne morale, le commerçant immatriculé, bénéficie également des mécanismes juridiques mis en place dans le cadre de la protection de son patrimoine contre les aléas de sa profession. Par ailleurs, l’immatriculation produit des effets à l’égard du commerçant qui viennent légitimer sa situation. Ainsi, elle permet à la personne physique d’avoir la qualité de commerçant de droit et à la société une existence juridique. De toute évidence, l’immatriculation est un instrument efficace pour la protection du commerçant. Toutefois, elle admet des limites si bien qu’elle joue un rôle ambigu. En effet, au-delà d’être au service du commerçant, l’immatriculation est une politique juridique mis en place pour protéger les tiers qui, en matière commerciale, s’oppose au commerçant. Cela s’explique clairement par le fait que l’immatriculation non seulement permet d’informer les tiers, mais aussi qu’elle présume la commercialité. De plus, les tiers grâce à l’immatriculation peuvent invoquer l’apparence à leur profit ou encore se prévaloir de la situation de fait engendré par son absence. The effectiveness of registration in protecting the trader is a reality in OHADA law. It is clearly manifested through the various advantages that registration provides to the trader. Once the registration formality has been completed, the trader will benefit from the advantages conferred on him by his status such as: the right to commercial property which automatically implies the right to renew the lease, the right to freedom of proof and the right to a shorter prescription. Unlike common law, the rules of commercial law applicable to the trader seem to be less rigid. Likewise, whether it is a natural person or a legal person, the registered trader also benefits from the legal mechanisms put in place to protect his assets against the vagaries of his profession. Furthermore, registration produces effects on the trader that legitimize his situation. Thus, it allows the natural person to have the quality of trader by law and the company a legal existence. . Obviously, registration is an effective instrument for the protection of the trader. However, it admits of limits so that it plays an ambiguous role. Indeed, beyond being at the service of the merchant, registration is a legal policy put in place to protect third parties who, in commercial matters, oppose the merchant. This is clearly explained by the fact that registration not only informs third parties, but also presumes marketability. In addition, third parties, through registration, can invoke appearance for their benefit or take advantage of the factual situation created by its absence.
Keywords: Commerçant; Immatriculation; RCCM; Registration; Third party; Trader

ضوابط إبرام الإتفاقيات بين شركة المساهمة والقائمين بإدارتها - العابد, توفيق; بوساحة, نجاة (Revue des Sciences Juridiques et Politiques, 2021)
يُسلِط هذا المقال الضوء على الضوابط التي تضمنها القانون التجاري الجزائري، في مجال إبرام الاتفاقيات بين شركة المساهمة والقائمين بإدارتها، بغية التوصل إلى معرفة مدى نجاعتها في ضمان حماية الشركة من العواقب الناجمة عن تعارض المصالح، وذلك من خلال التعرض بالوصف والتحليل للصور والإجراءات التي أقرتها النصوص القانونية الناظمة، بالإضافة إلى ما تم اعتماده في بعض التشريعات المقارنة. وقد خلصت الدراسة إلى أن المشرع الجزائري لم يحقق توازناً فعلياً بين سلطتي الإدارة والرقابة، نظرا لاعتماده على المراقبة البعدية التي أثبتت التجارب العملية عدم فعاليتها في معالجة قصور نظرية الوكالة. The article sheds light on the regulations of making agreements between the joint-stock company and its administrators in Algerian commercial law. In order to find out their effectiveness in ensuring that the company is protected from the consequences of conflicting interests, the images and procedures which are approved by the legal texts and have been adopted by comparative legislation were described and analyzed. The study concluded that the Algerian legislator did not achieve an effective balance between the authority of administration and that of censorship, due to the reliance on posteriori control, which practical experiences have proven ineffective in addressing the deficiencies of the agency theory.
Keywords: Administrators; Agreements; Conflicting interests; Joint-stock company; Regulations

L'arbitrabilité des litiges en droit des marchés financiers - Megam, Nadège Flore (International Multilingual Journal of Science and Technology, 2021)
Keywords: Arbitrage; Arbitration; Financial markets; Marchés financiers

The Role of Alternative Dispute Resolution (ADR) in Dispute Settlement of Logistics Activities - Quan, Gao (International Journal of Trend in Scientific Research and Development, 2021)
The Alternative Dispute Resolution (ADR) provides a non-litigation settlement mechanism for the parties of logistics activities. The advantages of ADR are highlighted in logistics dispute resolution due to the characteristics of logistics dispute and the difficulties faced in the litigation procedure. In the dispute resolution process, ADR means a simple, cost-efficient, and convenient method for the parties involved to settle disputes quickly, flexibly, and friendly. With its legitimacy and rationality, ADR should be the preferred choice for the parties involved in logistics dispute resolution.
Keywords: ADR; Alternative dispute resolution; Arbitrage; Arbitragem; Arbitration; Dispute settlement; Litigation procedure; Logistics activities; MARD; Mediación; Mediation; Mediação; Médiation

The effects of fraud by the beneficiary of the letter of guaranty on the obligation of the bank according to UNICITRAL 1995: a comparative study - Mustafa, Hamdi (UAEU Law Journal, 2021)
The research focuses on the effect of fraud of the beneficiary of the international letters of guarantee on the international commitment of the bank through UNICITRAL rules for 1995. Article 19 of UNCITRAL illustrates the cases where the guarantor is able to waive the payment to the beneficiary. UNICITRAL rules grant the bank the power to refuse payment when the claim of the client is supported by fake documents and so it keeps the balance between the different interests. UNICITRAL rules grant the bank the discretionary authority of the payment. The bank's role to maintain the confidence in the letter of guarantee and the characteristics of the letter of guaranty, which is independent and separate from the bank’s obligation towards the beneficiary of the letter of guaranty, is taken into account. In addition to that, these rules affirm the right of the client to take temporary judicial proceedings in the cases of exception from the payment in accordance with Article 19 of UNCITRAL. My research is divided into two sections, the first section is on the concept of fraud, its provisions and conditions according to UNICITRAL and the second section highlights the effects of the fraud on the bank’s commitment and means to protect its client. I have discussed the rules of international conventions of fraud and abuse of the authority by the beneficiary of the letter of guaranty before and after 1995. Finally, I referred to the beneficiary fraud in the Egyptian legislation

Le droit de rétention dans l'acte uniforme portant sûretés - Houedjissin, Arnaud (Afrilex : Revue d’étude et de recherche sur le droit et l’administration dans les pays d’Afrique, 2021)

The Relationship between International and Domestic Law in the Field of Attribution of Responsibility to a State in International Investment Disputes - Amidimehr, Elham; Seifi, Jamal (Public Law Researsh, 2021)
The attributability of actions to states within the context of investment treaty disputes and to focus on the roles played by international and domestic laws in such attributions have caught the attention of jurists in recent years. The ILC Draft Articles on Responsibility of States for Internationally Wrongful Acts, and particularly, article 3 points to the main outcome of this debate, where it does not consider domestic law irrelevant in internationally wrongful acts and stipulates that the issue is subject to international law and it will take into account the relevance of domestic law. Thus, although the characterization of an act of a State as internationally wrongful is an independent function of international law and such characterization is not affected by the characterization of the same act as lawful by domestic law, it does not mean that domestic law is irrelevant to such description; on the contrary, it may be related in various ways. The present article attempts to examine the challenging junction of domestic and international law with regard to the attributability of actions taken within the framework of investment treaties, specifically by state-owned and para-statal entities that exercise elements of state authority. قابلیت انتساب عمل به دولت در چارچوب اختلافات معاهده‌ سرمایه‌گذاری و تمرکز بر نقش‌هایی که حقوق بین‌الملل و حقوق داخلی در چنین انتسابی ایفا ‌می‌نمایند در زمره‌ مباحثی است که در سال‌های اخیر بسیار مورد ‌توجه حقوقدانان بوده و ماده 3 مواد کمیسیون حقوق بین‌الملل در ارتباط با مسئولیت دولت‌ها نیز بیانگر پیامد اصلی این بحث است که فی‌الواقع، حقوق داخلی را با مسأله متخلفانه بودن اعمال از حیث بین‌المللی بی‌ارتباط تلقی ‌ننموده، بلکه مقرر ‌می‌دارد مسئله مورد بحث، تابع حقوق بین‌الملل است لیکن حقوق بین‌الملل نیز خود تا حدِ ارتباط، حقوق داخلی را در نظر خواهد گرفت. بنابراین اگرچه توصیف خصوصیات یک عمل به عنوان عملی غیرقانونی از عملکردهای مستقل حقوق بین‌الملل است که تحت ‌تأثیر توصیف خصوصیات این عمل بموجب حقوق داخلی قرار نمی‌گیرد لیکن این گفته بدین معنی نیست که حقوق داخلی با توصیف عمل متخلفانه‌ بین‌المللی بی‌ارتباط ‌است؛ بالعکس، ممکن ‌است به طرق مختلفی به آن مرتبط‌ باشد. در این مقاله سعی بر‌ آن است که تلاقی چالش‌برانگیز حقوق داخلی و حقوق بین‌الملل در بحث قابلیت انتساب اعمال ‌صورت ‌گرفته در چارچوب معاهدات سرمایه‌گذاری توسط ارگان‌های دولتی و نهادهای نیمه‌دولتی که عناصر اختیارات دولتی را اعمال می‌نمایند مورد واکاوی قرار‌ گیرد.
Keywords: Attribution; Domestic Law; International Arbitration; International Investment Treaties; International Law; حقوق بین‌الملل; حقوق داخلی; داوری بین‌المللی; معاهدات سرمایه‌گذاری بین‌المللی; کلیدواژگان انتساب مسئولیت

A Reflection on the Invalidation of Patents in the Light of Constituent Elements of Indirect Expropriation under Foreign Investment Law - Rahbari, Ebrahim; Shahabi, Mahdi; Falahati, Soroosh (Public Law Researsh, 2021)
Patents are considered as investments protected under the International Investment Law. Although, these properties are protected under the principle of territoriality, similar to other investments, they can be expropriated as a result of host states’ regulatory measures inconsistent with protection standards stemming from foreign investment protection regulations and treaties including fair and equitable treatment and legitimate expectations of foreign investors. Considering the fact that few arbitration awards have been issued by arbitration panels in this regard, it is yet difficult to claim there is a strong precedent in International Investment Law. Nevertheless, reflecting the provisions of international regulations, the stance of the domestic law and the most important relevant case, this article provides the most significant elements of indirect expropriation as well as existing doctrines in this respect and further investigates whether invalidation of patents can amount to indirect expropriation. It will also be mentioned that despite the fact that according to several foreign investment protection treaties, invalidation of patents shall not be subject to regulations regarding indirect or creeping expropriation, the final determination lies with the arbitration panel. یکی از مصادیق سرمایه‌گذاری خارجی مورد حمایت در حقوق بین‌الملل سرمایه‌گذاری، اختراعات است. این دسته از دارایی‌ها علی‌رغم به رسمیت شناخته شدن در پرتو اصل سرزمینی بودن حمایت، همانند سایر سرمایه‌گذاری‌ها می‌توانند تحت تدابیر حاکمیتی دول میزبان که مغایر با استانداردهای حمایتی نشأت گرفته از قوانین و معاهدات بین‌المللی حمایت از سرمایه‌گذاری خارجی همچون شرط رفتار عادلانه و منصفانه و صیانت از انتظارات مشروع و معقول سرمایه‌گذار می‌باشند، با خطراتی همچون سلب مالکیت مواجه شوند. نظر به صدور آرای معدود مراجع بین‌المللی در این خصوص، سخن گفتن از شکل‌گیری رویه‌ای متقن در این راستا دشوار می‌باشد. با این حال، در این نوشتار ضمن بررسی مهمترین عناصر متشکله سلب مالکیت غیرمستقیم و دکترین‌های موجود در این زمینه، به بررسی قابلیت تطبیق ابطال گواهی ثبت اختراع با سلب مالکیت غیرمستقیم پرداخته و با تشریح مقررات برخی اسناد بین‌المللی، موضع حقوق داخلی و مهم‌ترین پرونده مربوط به این موضوع در حقوق سرمایه‌گذاری خارجی در ابعاد گوناگون آن مداقه نموده و در نهایت به این نتیجه خواهیم رسید که حتی در صورت مستثنی نمودن ابطال گواهی ثبت اختراع از مقررات مربوط به سلب مالکیت در معاهدات حمایت از سرمایه‌گذاری خارجی، تشخیص نهایی تحقق سلب مالکیت با دیوان داوری است.
Keywords: Elements of indirect expropriation; Foreign investment; Indirect expropriation; Intellectual property; Invalidation of patents; ابطال گواهی ثبت اختراع; حقوق مالکیت فکری; سرمایه‌گذاری خارجی; سلب مالکیت غیرمستقیم; عناصر سلب مالکیت غیرمستقیم

Mediation: Is There a More Promising Future? The Case of the Cairo Business Community - Soliman, Cherine (Arab Journal of Administration, 2021)
In an era of economic distress, some organizations have found refuge and growth potential in cooperation. Mediation, a highly recommended cooperative concept, has been enabled in certain countries but not all. Some applications lacked local cultural support making it, despite government efforts, a failure to launch. In this article, we investigate attempts to launch mediation in the Cairo Business Community (CBC). This study enabled us to revisit how Egyptian culture was prototyped by Hofstede and to question its representativeness. Hofstede has consistently described Egyptian culture as being highly cooperative / collectivist but our observations indicate that this culture is now more of an individualistic / competitive type, due to the tremendous economic difficulties that Egyptian society is going through. These difficulties and their impact on culture are at the heart of the explanation of the failure to launch mediation in the CBC.
Keywords: Cairo Business Society; Conflict Resolution; Culture; Egypt; Mediation

Combating insolvency and business recovery problems in the oil industry: proposal for improvement in Nigeria's insolvency and bankruptcy legal framework - Olujobi, Olusola Joshua (Heliyon, 2021)
Insolvency and business recovery laws in Nigeria have not evolved to incorporate reorganisation, reforming insolvent oil firms' operations to boost commercial oil firms' steadiness and economic suitability like other moderately developed countries. In Nigeria, liquidation is understood by many as the panacea to indebtedness. The research evaluates the Nigerian insolvency and business recovery legal regime to sustain indebted oil firms from economic shocks due to the global decline in the oil price to avert imminent business failures due to insufficient cash flows. The aim is to fill the gaps in Nigeria's insolvency and business recovery laws by recommending a model for the sustenance of oil firms and to suggest the reform of the gaps identified in the existing laws and the extant literature on the subject. The paper opted for conceptual legal review, comparative legal and policies analyses of solvency and business recovery legislations in Nigeria, Malaysia, India, South Africa, the United Kingdom and the United States. These nations were designated for this study because their insolvency and business recovery legal regime are business rescued driven, not winding up centred. The study is library research-based to address some of the flaws in Nigeria's insolvency and business recovery laws. The study finds that Nigerian legislation on insolvency is flawed in oil firms' salvage, improvement and rearrangement. It ends that, statutory bodies in the designated case study nations are efficient than those in Nigeria due to the strong political will of their governments in supporting insolvent oil firms for successful financial recovery, to safeguard jobs, to protect creditors and to enhance the wealth of their nations through sound business recovery policies and laws. The study, advocates, remodel of Nigeria's insolvency and business recovery legislations and policies in compliance with the international standards on insolvent oil firms salvaged and creditors focused policies for a robust economy. The study concludes with the recommendation for further study to consider quantitative analysis research methodology to project further scholarship on the subject.
Keywords: Creditor; Insolvency and business recovery laws; Nigeria; Oil firms

Contourner l'immunité d'exécution des personnes morales de droit public : petites recettes privatistes en droit camerounais - Kamgaing, Pierre-Claver; Fotso Djomkam, Darius Kevin (Horizons du droit : Revue de l'association française des docteurs en droit, 2021)

La société nationale après le dialogue des normes - Ndiaye, Cheikh Abdou Wakhab (Revue d’étude et de recherche sur le droit et l’administration dans les pays d’Afrique, 2021)
L’actionnariat n’est pas l’apanage des personnes privées. L’Etat actionnaire est devenu une réalité manifeste. Lorsqu’il est le seul à détenir les titres sociaux d’une société, le droit sénégalais qualifie celle-ci de société nationale pour lui appliquer un régime dérogatoire. Se pose alors la question de l’articulation entre un tel régime et celui posé par l’OHADA. Quel droit pour la société nationale ? Réceptacle de deniers publics, la société nationale est-elle appréciée comme une simple société commerciale ? Shareholding is not the prerogative of private individuals. The State as shareholder has become an obvious reality. When it is the only one to hold the shares of a company, Senegalese law qualifies it as a national company in order to apply a derogatory regime to it. This raises the question of the articulation between such a regime and that of OHADA. Which law for the national company? As a recipient of public funds, is the national company appreciated as a simple commercial company?

Afri̇ka Ülkeleri̇ Hukuku Düzenlemeleri̇nde İrade Muhtari̇yeti̇ - Dürgen, Betül (Africania, 2021)
Çağdaş hukuk düzenlerinde geniş yankı uyandıran irade muhtariyeti ilkesi, kimi zaman maddi hukuk hükümlerinde sözleşme özgürlüğü olarak kendini belli ederken kimi zaman da milletlerarası özel hukuk alanında taraflara hukuk seçimi imkânı ile gündeme gelmektedir. Bazı ülkelerin sınırlandırdığı ölçüde serbest ekonomik düzenlerine dahi etki eden irade muhtariyeti ilkesi, hukukların yeknesaklaştırıldığı kadarıyla uygulanabilir hale gelmektedir. Çalışmamıza konu olan Afrika kıtası ülkelerinde, hukukun yeknesaklaştırılması gereği bölgede anlaşılmış olup gerekli adımların atıldığı OHADA kanunları ile açığa çıkarılmıştır. Bunun dışında yer yer milletlerarası özel hukukta genel olarak kabul görmüş bağlama noktaları dışına çıkan ülke bazında uygulamaların söz konusu olduğu da görülmektedir. Çalışmamızın amacı irade muhtariyeti prensibinin milletlerarası özel hukuka yansıması olan hukuk seçiminin Afrika’da uygulanabilir olup olmadığını tespit etmektir. Bu tespiti yapmak Afrika ülkelerindeki çeşitli uygulamaların çağdaş düzenlemeler ile karşılaştırılmasını gerektirmiştir
Keywords: OHADA; Party autonomy; applicable law; choosing law; hukuk seçimi; irade muhtariyeti; milletlerarası özel hukuk; private international law; uygulanacak hukuk

L'assurance de responsabilité de l’armateur et du chargeur dans le Transport de Marchandises Dangereuses (TMD) en zone CEMAC - Nestorine, Magne Anne (Espace Géographique et Société Marocaine, 2021)
Comment répare-t-on les dommages causés par les marchandises dangereuses ? Quels sont les principes qui gouvernent cette réparationsurtout au niveau de la quantification des indemnités à verser aux victimes? Ces questions trouveraient bien une réponse dans une étude consacrée au transporteur. Par contre, concernant le chargeur de marchandises dangereuses, aucun texte ne prévoit de façon cohérente et suffisamment claire, des régimes de réparation et de quantification des indemnités. Le flou juridique existant en la matière à conduit à s’intéresser aux mécanismes d’assurance existant. Les législations sur le transport de marchandises dangereuses par mer n’exigent pas de façon spécifique une assurance de responsabilité civile du chargeur. Le Code CIMA par exemple ne régit pas les assurances maritimes. L’assurance qu’on peut qualifier de classique et qui peut concerner tous les opérateurs du transport de marchandises dangereuses, bien que revêtant une importance à nul autre comparable, n’a pas retenu l’attention du législateur. On a donc assisté au développement des clubs de protection et indemnisation propres aux armateurs, qui essayent tant bien que mal de compenser les insuffisances textuelles. Cet état de chose a permis de donner à l’assurance une double facette. L’urgence de l’institutionnalisation d’une assurance de responsabilité civile se fait donc ressentir dans la zone CEMAC. How is the damage caused by dangerous goods repaired? What are the principles that govern this compensation, especially when it comes to quantifying what should be paid to victims? These questions would be answered in a study of the carrier. Conversely, as far as the shipper of dangerous goods is concerned, no text provides in a coherent and sufficiently clear way, schemes of repair and quantification of indemnities. The legal uncertainty in this area has led to an interest in existing insurance mechanisms.Legislation on the carriage of dangerous goods by sea does not specifically require shipper's liability insurance. The CIMA Code for example excludes marine insurance. The insurance which can be described as classic and which may concern all transport operators of dangerous goods, although of greater importance than any other, has not drawn the attention of the legislator. We have therefore seen the development of protection and compensation clubs specific to shipowners, who are trying somehow, to compensate for textual inadequacies. This state of affairs has given insurance a double facet. In particular, as far as the shipper is concerned, the urgency of the institutionalization of a liability insurance related to him is felt in the CEMAC zone.
Keywords: Armateurs; Assurances maritimes; Chargeur; Civil liability; Compensation; Damage; Dommages; Indemnisation; Marine insurance; Responsabilité civile; Shipowners; Shipper; Transport

The Impact of Trade Openness and Foreign Direct Investment on Economic Welfare in sub-Saharan Africa - Adegboye, Folasade Bosede; Adesina, Olumide Sunday; Olokoyo, Felicia Omowunmi; Ojeka, Stephen Aanu; Akinjare, Victoria Abosede (International Journal of Financial Research, 2021)
The sub-Saharan African region is characterized by a high relative degree of openness to trade. The region is also identified with increased inflows of foreign investments with no significant welfare improvement. Economic development emphasizes that the lack of domestic investment in the developing economies could be boosted by trade openness and inflow of Foreign Direct Investment (FDI) for impactful enhancement of capital formation. In this article, the impact of trade openness and foreign capital inflow on economic welfare was examined on a sub-regional analysis for sub-Saharan Africa. The study also appraised the effect of openness to trade and FDI inflow on the region's economic welfare. The data for 30 countries from 2000 to 2018 were collected and analyzed, with the Generalized Least Square (GLS) technique to fit the model developed. The study showed that openness to trade has a significant impact on economic welfare for all sub-Saharan Africa regions, while FDI is only significant for the Western sub-region. Hence, the study recommends that the government of the countries in the sub-Saharan Africa region should boost trade openness to enhance efficiency in productivity, and improve industrial development.
Keywords: Economic Welfare; Foreign direct investment; Sub-Saharan Africa; generalized least square; sub-regional analysis; trade openness

L'action en revendication dans les procédures collectives OHADA - Kamsu Nenpe, Judith Merline (International Multilingual Journal of Science and Technology, 2021)
L’action en revendication en droit des procédures collectives OHADA a connu un véritable toilettage lors de la réforme de l’Acte uniforme du 10 septembre 2015 portant organisation des procédures collectives d’apurement du passif (AUPCAP). Soumise à la production préalable de créance, il était difficile de faire la distinction dans l’espace OHADA entre le revendiquant et le créancier. L’AUPCAP nouveau a le mérite d’avoir dissocié l’action en revendication de la production de créance, tant il était incongru de lier ces deux formalités qui ont des objets différents. La revendication a pour objet de faire reconnaitre le droit de propriété tandis que la production vise à rendre la créance opposable à la procédure. Cette dissociation rend la procédure de l’action en revendication plus lisible et plus sécurisante pour les revendiquants. Par ailleurs le législateur OHADA a le mérite d’avoir élargi l’assiette des revendications, ce à travers le nouveau contenu donné à la notion de « biens réservés ». L’incorporation du bien à un autre bien, sa fongibilité ne sont plus incompatibles avec l’action en revendication, même si le silence de ce dernier sur la problématique des biens transformés laisse encore le revendiquant sur sa faim. The claim in the insolvency law OHADA has known a real grooming during the reform of the uniform act of 10 September 2015 relating to the collective proceedings for wiping off debts. Subject to the pre-production debt, it was difficult to make the distinction in the OHADA zone between the claimant and the creditor. The AUPCAP again has the merit of having dissociated itself from the claim of the production of debt, as long as it was incongruous to link these two formalities that have different objects. The claim was for a declaration of the right of property, while the production aims to make the debt enforceable in the procedure. This dissociation makes the process of the claim more readable and more secure for the claimants. Moreover, the legislature OHADA t has the merit of having extended the base of the claims, this through the new content given to the notion of " vested property ". The incorporation of the property to another property, its fungibility is no longer incompatible with the claim, even if the silence on the issue of processed goods still leaves the claimant on his hunger.

Les paradoxes de l'arbitrage institué par la Conférence Interafricaine des Marchés d'Assurances (CIMA) - Sindjui Siani, Brice Carlin (International Multilingual Journal of Science and Technology, 2021)
La constance dans l’arbitrage est sans doute la volonté dans le recours à ce mode de résolution de conflits. C’est parce que les parties trouvent un intérêt à l’arbitrage, qu’elles décident d’échapper à la compétence de principe des juridictions étatiques. Or, ce bel édifice est remis en cause par le législateur CIMA à l’article 276 par l’instauration d’une Commission Nationale d’arbitrage au sein des États membres dont les assureurs sont obligés de saisir lorsque nait un différend dans l’exercice des recours subrogatoires entre eux. Le paradoxe arbitral ainsi analysé comme ce qu’il est convenu d’appeler l’ « arbitrage forcé » n’empêche pas toute fois d’entrevoir dans ledit arbitrage institutionnel, un instrument au service de la justice et des assureurs tant les vertus sont variées.
Keywords: Arbitrage; Arbitration; Assureurs; CIMA; Commission Nationale d’Arbitrage; Insurers; National Commission of Arbitration; Recours subrogatoire; Recourse of subrogation

Le Cameroun et les enjeux de la réforme de la législation sur le transport maritime de marchandises - Tchimmogne, André (Espace Géographique et Société Marocaine, 2021)
La réforme de la législation sur le transport maritime au Cameroun et dans la zone CEMAC était attendue. En effet, à la défaveur de la coexistence sur le plan international de la Convention de Bruxelles et des Règles de Hambourg, ainsi que de la nécessité d’arrimer la législation à l’évolution de la pratique, il était nécessaire de toiletter la législation en vigueur. L’adoption des Règles de Rotterdam s’inscrit ainsi dans un courant économique et juridique favorable à l’uniformisation, à la modernisation et à la prise en compte des pratiques contractuelles jusqu’alors dénuées de toute réglementation. La ratification du texte international par le Cameroun procède également d’une politique économique d’un Etat épris de développement, qui a fait de sa participation au commerce extérieur, un axe majeur de son émergence. Cette évolution juridique nécessaire mais insuffisamment encadrée s’effectue dans un contexte réglementaire tous azimuts. Ceci est susceptible de conduire non seulement à des conflits de lois, mais également à l’hibernation juridique du code communautaire de la marine marchande CEMAC, généralement non appliqué. Mots clés : Transport maritime, législation, enjeux, reforme. The reform of the legislation on maritime transport in Cameroon and in the CEMAC zone was expected. Indeed, to the detriment of the international coexistence of the Brussels Convention and the Hamburg Rules, as well as the need to align legislation with the development of practice, it was necessary to tidy up the legislation force. The adoption of the Rotterdam Rules is thus part of an economic and legal trend favorable to standardization, modernization and the taking into account of contractual practices hitherto devoid of any regulation. Cameroon's ratification of the international text is also the result of an economic policy of a development-loving state, which has made its participation in foreign trade a major axis of its emergence. This necessary but insufficiently supervised legal development is taking place in an all-out regulatory context. This is likely to lead not only to conflicts of laws, but also to the legal hibernation of the community code of the CEMAC merchant navy, generally non enforced.
Keywords: Maritime carriage; Transport maritime

Les tentatives de régulation publique des blockchains - La responsabilisation des acteurs par une régulation a minima des smart contracts ? - Arrouas, David (Revue francophone de la propriété intellectuelle, 2021)
Keywords: Intellectual property

Les conditions de la régulation publique des blockchains - Le droit au défi des blockchains - Auby, Jean-Bernard (Revue francophone de la propriété intellectuelle, 2021)
Keywords: Intellectual property

Legal Translaboration for Effective Intercultural Communication - Bell Mandeng, Adrien (Scientific Annals of Alexandru Ioan Cuza University, 2021)
The European-inspired bilingualism and bi-legal system in Cameroon lead to an irregular profile and may be interesting for the European Union (EU) in its quest for preservation of intercultural processes through translation. The Organization for the Harmonization of Business Law in Africa (OHADA) of which Cameroon is part is only affiliated to Civil Law. However, the two legal systems employed in Cameroon (where both Civil Law and Common Law are used) are based on a balance in what concerns the conceptual, epistemic and stylistic representation. Intercultural dysfunction is the consequence of the lack of methodology in legal translation. Collaboration between legal translators and practitioners is key to adopt an agreed-upon model in multilingualism.
Keywords: Culture; History; Intercultural communication; Legal translaboration; OHADA

Propriété intellectuelle et droit civil : Approche française - Binctin, Nicolas (Les Cahiers de propriété intellectuelle, 2021)
Le droit de la propriété intellectuelle français constitue un régime de droit spécial des biens. Si les conditions d’appropriation sont spécifi ques et ne s’appuient guère sur le droit civil, le régime de la propriété, la circulation et l’exploitation des biens intellectuels font, en revanche, largement appel au droit commun civil, princi palement par le biais d’un mécanisme supplétif et, parfois, par le biais d’un renvoi express. Cet article propose quelques illustrations de ce lien constant qui permet, d’une part, d’apporter à la propriété intellectuelle les compléments de régime dont elle a impérativement besoin et, d’autre part, de confronter les solutions du droit civil aux meubles incorporels.
Keywords: Droit civil; Intellectual property; Propriedade intelectual; Propriété intellectuelle

Gestion collective : regards au prisme de la DAMUN - Carre, Stéphanie (Revue francophone de la propriété intellectuelle, 2021)
Keywords: Intellectual property

Chronique de droit du dommage corporel (avril 2020 à mars 2021) - Cayol, Amandine (Bulletin Juridique des Assurances, 2021)

Transition from Local Accounting Standards to International Accounting Standards: A Comparison Between the OHADA Member Countries and Turkey - Diallo, Amadou Thierno; Çevi̇K, Zülküf (Yorum Yönetim Yöntem Uluslararası Yönetim Ekonomi ve Felsefe Dergisi, 2021)
This study tries to get a clear grasp of the factors that might play positively or negatively in a country’s convergence or adoption of the international financial reporting standards (IFRS). Through a comparative analysis between Turkey and the OHADA countries and based on the existing literature, the transition process towards the IFRS and challenges faced by each one is discussed from a historical perspective to the level of development. As a result, it is understood that the adoption or convergence towards the IFRS can be a challenging and a long-term process requiring multiple adjustments. Also, countries may differ in terms of historical past, level of development, cultural and socio-economic aspects which can all influence their transition. In addition, given the lack of study on the new adoption of the IFRS in the OHADA countries, this paper will contribute to filling the gap in the literature on the transition process. Furthermore, it will help countries which are in their early stage of the transition process to avoid some missteps and learn from others experience to get better prepared for a successful shift towards a fully IFRS compatible accounting system as has done Turkey. Bu çalışma, bir ülkenin uluslararası finansal raporlama standartlarına (IFRS) yakınsaması veya tam olarak benimsemesinde olumlu veya olumsuz rol oynayabilecek faktörleri tespit etmeyi amaçlamaktadır. Türkiye ile OHADA ülkeleri arasında karşılaştırmalı bir analiz yoluyla ve mevcut literatüre dayalı olarak, UFRS'e geçiş süreci ve bu süreçte karşılaşılan zorluklar, tarihsel bir perspektiften tartışılmaktadır. Sonuç olarak, IFRS’in benimsenmesi veya uyumlaştırılmasının zorlu ve birçok ayarlama gerektiren uzun vadeli bir süreç olduğu anlaşılmaktadır. Üstelik bu güçlükler, ülkelerin geçişlerini etkileyebilecek, tarihsel geçmiş, gelişmişlik düzeyi, kültürel ve sosyo-ekonomik yönler açısından farklılık gösterebilir. Buna ek olarak, OHADA ülkelerinde IFRS'in yeni benimsenmesine ilişkin çalışma eksikliği göz önüne alındığında, bu makale geçiş süreciyle ilgili literatürdeki boşluğun doldurulmasına katkıda bulunacaktır. Ayrıca, geçiş sürecinin erken aşamalarında olan ülkelere bazı yanlış adımlardan kaçınmalarına ve diğerlerinin deneyimlerinden öğrenerek, Türkiye'de olduğu gibi tamamen IFRS uyumlu bir muhasebe sistemine başarılı bir geçiş için daha iyi hazırlanmalarına yardımcı olacaktır.
Keywords: Accounting standards; Approche comparée; Comparison; Comptabilité; International Accounting Standards; Local Accounting Standard

La réforme du droit des marques en France : aspects du droit substantiel - Dorey, Valérie; Pelèse, Christophe (Revue francophone de la propriété intellectuelle, 2021)
Keywords: Intellectual property

Le secteur informel en Afrique - Epoma, Yolaine Samantha (Revue de Recherches en Economie et en Management Africain, 2021)
Le secteur informel est depuis longtemps une des préoccupations majeures dans les pays africains, à cause de la place dominante qu’il y occupe (I). Il est perçu par certains comme un véritable goulot d’étranglement pour les économies du continent. Soucieux de leur place dans le monde des affaires, de l’attractivité de leur territoire, les pays africains recherchent sans cesse des stratégies pour réussir à maîtriser le secteur informel afin de mettre en place des politiques qui lui sont adaptées, car son expansion agit sur le développement des pays africains (II). La solution la mieux préconisée est de trouver des mesures d’accompagnement pour encadrer ce secteur, faciliter son intégration dans le secteur formel. Autrement dit, la formalisation des activités économiques informelles (III) est l’objectif principal des Etats africains.
Keywords: Activités économiques informelles; Afrique; Formalisation; Secteur informel

The Contents of the Articles of Association as a Document used in the Creation of Companies in Cameroon under the OHADA Law - Eposi, Gladys Nku Tiku (International Journal of Science and Research, 2021)
This study unveils that the creation of companies in Cameroon is been regulated by the OHADA[1], law under the Uniform Act on Commercial Companies and Economic Interest Groups (UACCEIG) which says, every company must have its own Articles of Association [2]. The Articles of Association is a document that contains the internal regulation for the management of the company’s affairs. [3] The articles of association are the contracts between the shareholders and the company and among the shareholders themselves. [4] The questions raised are what are the requirements common in the Articles of Association of all companies under OHADA Law? What effect do the AOA has? The study adopted an analytical approach which has led to the finding that the AOA under OHADA, is similar to the MOA [5] in most English speaking countries, but a major difference in that UACCEIG has limited the life span of the company to 99years while under English company law, a company goes on for an indefinite period. [6] The life span of the company should not be limited due to the principle of perpetual succession. The UACC seem to have concurred with some aspects of the Common Law, making the UACC an applaudable law reform.
Keywords: Articles of association; Cameroon; Commercial companies; Notarised deed; OHADA Law

Experimenting with international commercial dispute resolution - Erie, Matthew S; Bookman, Pamela K (AJIL Unbound, 2021)
In this essay, we describe the overlapping phenomena of new legal hubs (NLHs), international commercial courts, and arbitral courts. We survey their impact on the law and geopolitics of international commercial dispute resolution, identifying key issues these new dispute resolution institutions raise. While the rise of international commercial courts spans authoritarian and liberal states, Western and Asian states, common law and civil law traditions, it also highlights and builds upon regional differences. We question the assumption that the establishment of new courts is always consistent with an increase in the rule of law, particularly in non-democratic states. We close with thoughts about the potential influence and future role of these institutions. Some of the procedural innovations discussed here may lead to shifts in international commercial dispute resolution for years to come, but the question of whether there is sufficient demand for these new institutions lingers.

Les conditions de la régulation publique des blockchains - La régulation par la blockchain - Favreau, Amélie (Revue francophone de la propriété intellectuelle, 2021)
Keywords: Intellectual property

Corporate social responsibility and management of oil related conflict in Host Communities of Niger Delta Region, Nigeria - Gbali, Kenneth Chisom; Weli, Vincent Ezikornwor; Mmom, Prince Chinedu (World Journal of Advanced Research and Reviews, 2021)
The study sought to examine the Corporate Social (CSR) and management of oil related conflicts in Host Communities of the Southern States. Corporate Social Responsibility is the commitment of businesses to contribute to sustainable economic development by working with employees, the local community and the society at large to improve their lives in ways that are good for business and for development. The study was guided by three research objectives, three research questions and three hypotheses. The design adopted for this study is exploratory and descriptive research design and was conducted in Bayelsa, Delta and Rivers State in Nigeria. The population of this study comprised of 15,245,247 residents in Bayelsa, Delta and Rivers State in Nigeria. The instrument for data collection was a set of structured questionnaire. Data derived from the field were analyzed using the Statistical Package for Social Sciences (SPSS) version 23.0. And statistical tools such as mean and standard deviation were used to respond to the research questions, while inferential statistical tool of independent sample T-test was used to test the hypotheses at 0.05 level of significance. Findings from the study showed that there is a significant difference in the mean ratings of male and female respondents on the level of relationship between IOC’s and hosts Communities in Niger Delta Region, Nigeria ((P=0.738>0.05), df (400) =. -0.49273, p=0.738); there is a significant difference in the mean ratings of male and female respondents on the on CSR programs carried out by IOCs in hosts Communities in Southern Nigeria (P=.117>0.05), df (400) = -401.618, p=.117); further findings showed that there is a significant difference in the mean ratings of male and female respondents on the Factors causing conflict between oil companies and host communities in Southern, Nigeria (P=0.775>0.05), df (400) =382.256 p=0.775). Based on the findings of the study, it was recommended that host communities should be integrated into the planning process, a paradigm shift from planning for to planning with the host Communities, amongst others.
Keywords: CSR; Corporate Social Responsibility; Host communities; Oil Related Conflict; Oil companies; Southern Nigeria

COVID-19 and Comparative Corporate Governance - Gelter, Martin; Puaschunder, Julia M. (The Journal of Corporation Law, 2021)
With the pandemic caused by the novel coronavirus SARS-CoV-2 raging around the world, many countries’ economies are at a crucial juncture. The COVID-19 external shock to the economy has the potential to affect corporate governance profoundly. This Article explores its possible impact on comparative corporate governance. For an economy to operate successfully, a society must first find a politically sustainable social equilibrium. In many countries, historical crises—such as the Great Depression and World War II—have resulted in a reconfiguration of corporate governance institutions that set the course for generations. While it is not yet clear whether COVID-19 will have a similar effect, it is possible that it will change patterns of what kind of firms are -from an evolutionary perspective- likely to survive, and which ones are not. We argue that to some extent, it will accelerate ongoing trends, whereas in other areas it put corporations on an entirely new course. We observe three trends, namely the need for resilience, a growth of nationalist policies in corporate law, and an increasing orientation toward “stakeholder” interests. First, firms will have to become resilient to the crisis and consequently long-term oriented. Corporations that are not operating merely on an arm’s length capital market basis but are integrated into a network, generated by core shareholders, state ownership, or bank lending may be more likely to survive. In addition, firms are beginning to interact with their workforce differently in their attempts to maintain what could be called “healthy human capital.” Second, we are likely to see a resurgence of nationalism in corporate governance to ensure that foreign ownership and interconnected supply chains do not put national security at risk. Third, the existing critiques of inequality but also climate change awareness will accelerate the trend toward a broadening of corporate purpose toward “stakeholderism” and public policy issues. As in the past years, institutional investors acting as “universal owners” will play a role in shaping this trend.
Keywords: Behavioral; COVID-19; Climate change; Corporate governance; Corporate law; Economic protectionism; Evolutionary theory; Free cash flow; Green New Deal; Human capital; Inequality; Nationalism; Ownership structure; Relational finance; Shareholder primacy; Stakeholder theory; Varieties of capitalism

L’évolution de la protection des signes de qualité en Europe - Goffic, Caroline Le (Revue francophone de la propriété intellectuelle, 2021)
Keywords: Intellectual property

Les exceptions de fouille de textes et de données dans la directive 2019/790 du 17 avril 2019 : la fragilité d’un équilibre apparent - Kahn, Anne-Emmanuelle (Revue francophone de la propriété intellectuelle, 2021)
Keywords: Intellectual property

The Power of an Arbitral Tribunal to Determine Its Own Jurisdiction in International Commercial Arbitration - Kamanga, Patricia N. S. (Beijing Law Review, 2021)
Keywords: Arbitration Agreement; Competence-Competence; Jurisdiction; Party Autonomy; Power

Global Civil Procedure - King, Alyssa S. (SSRN Electronic Journal, 2021)
A “global” civil procedure has emerged and found its way into debates over procedural reform in both international and domestic arenas. Global civil procedure includes the procedural rules, practices, and social understandings that govern transnational litigation and arbitration. A global civil procedure norm is a norm adopted across courts or arbitration providers with the purpose of making that jurisdiction or provider more competitive in attracting transnational litigation or arbitration. Global civil procedure norms are at stake in multiple present trends and debates, including model laws in commercial arbitration, the procedure of international tribunals, the debate over investment dispute resolution, the rise of courts oriented towards international litigation, and sprawling litigation spanning multiple jurisdictions and fora. On a surface level, the values reflected in global civil procedure seem to be roughly the same across jurisdictions. A common language has emerged around competition for litigation business and procedure values such as efficiency, certainty, and impartiality. Yet different legal systems do not necessarily agree on the purpose of various shared elements of global civil procedure. For democracies, for instance, the purpose of procedural reforms might be to facilitate access to justice. Other countries may favor the same reforms because they facilitate top-down administrative control of judges. Surface agreement can submerge divergent logics that may ultimately lead to very different applications of harmonized rules. This Article begins by introducing the concept of global civil procedure, who uses it, and how. Next, it considers several examples of the phenomenon including conflicts of interest rules for adjudicators, aggrega tion, and discovery or disclosure rules. Finally, it considers the limits of global civil procedure. Although the rhetoric of procedural competition can be heard across systems, procedural values do not necessarily translate both in terms of enduring divisions between legal traditions and in terms of applications by current political regimes.

Les usages publics de la blockchain - Blockchain et administration de la justice - Labbé, Thibaut (Revue francophone de la propriété intellectuelle, 2021)
Keywords: Intellectual property

The job security of employees of financially distressed companies - Loubser, Mieka E.; Garbers, Christoph (South African Mercantile Law Journal, 2021)
This contribution considers the legislative regulation of the job security (which boils down to preservation of employment) of employees in case of financial distress of a company. It juxtaposes the legislative regulation of four interrelated processes a company may engage in where it finds itself in financial distress, namely a voluntary internal restructuring (especially retrenchment), the transfer of the business or part of the business, business rescue and winding up. The legislative endeavour to preserve the job security of employees in all these processes is described and analysed. The discussion shows that room exists for companies to circumvent this protection and, to the extent that the protection does apply, that it remains difficult for employees to ultimately challenge the substance of decisions negatively affecting their job security. The main protection for employees in all these processes is procedural in nature and to be found in their rights to be informed of and consulted prior to decisions negatively affecting them. In this regard, business rescue is the most employee-friendly process. Participation in this process by employees, however, requires a fine balance as it may be self-defeating and lead to winding up and the permanent loss of jobs.
Keywords: Business rescue; Dismissal; Insolvency; Job security; Labor laws and legislation; Liquidation; Merger; Operational requirements; Retrenchments; Transfer of a business

L’état au défi des blockchains - Rapport de synthèse - Macrez, Franck (Revue francophone de la propriété intellectuelle, 2021)
Keywords: Intellectual property

Le financement de l’arbitrage par les tiers - Makhlouf, Amel (Revue internationale de droit comparé, 2021)
ruit de la pratique anglo-saxonne, le financement de l’arbitrage par un tiers financeur connaît un essor significatif tant à l’échelle nationale qu’internationale. Intervenu en France ces dernières années, ce mécanisme permet à un tiers (fonds d’investissement, société de financement spécialisée…) de financer une partie ou la totalité des frais relatifs à une procédure arbitrale tels que les frais d’avocats, d’experts, de témoins, d’arbitres ainsi que ceux liés à l’exécution de la sentence arbitrale. En cas de succès, le tiers financeur perçoit en contrepartie un pourcentage sur les dommages et intérêts alloués par la sentence arbitrale à la partie financée . Bien que dans une large majorité des cas le tiers financeur intervienne en faveur de la partie demanderesse, il peut aussi intervenir en faveur du défendeur ayant formulé une demande reconventionnelle. Le tiers financeur assume seul les risques financiers liés à la procédure. Si la partie financée n’obtient pas gain de cause à l’issue de la procédure arbitrale, le tiers ne percevra donc aucune rémunération et ne sollicitera auprès de son client aucun remboursement des frais qu’il aura avancés pour lui.

Les délimitations maritimes Turquie-gouvernement d'entente nationale libyen et Grèce-Égypte dans leur contexte régional - Marghelis, Aris (Neptunus, 2021)

Le 27ème considérant de la Directive et le 21ème du RMUE : un nouveau souffle pour l’exception de parodie en droit des marques ? - Martin, Stefan (Revue francophone de la propriété intellectuelle, 2021)
Keywords: Intellectual property

Impact des attributs du pouvoir discrétionnaire des dirigeants sur la performance financière de leur entreprise dans le contexte camerounais - Mbaduet, Joséphine; Djoutsa Wamba, Léopold; Sahut, Jean-Michel; Teulon, Frédéric (Management international, 2021)
Cet article propose d’évaluer l’impact des attributs du pouvoir discrétionnaire des dirigeants sur la performance financière de leur entreprise dans le cadre d’un pays doté d’un faible système de gouvernance, le Cameroun. L’analyse des résultats montre que le dirigeant qui mobilise ses compétences managériales spécifiques, investit dans des actifs ayant un lien avec ses connaissances ou encore cherche des soutiens au sein de son réseau relationnel obtient de meilleures performances que celui qui ne le fait pas. Seuls les dons aux administrateurs ont un effet négatif sur la performance financière. Toutefois, les dirigeants camerounais sont contraints dans leur pouvoir discrétionnaire par certains contre-pouvoirs, et le niveau d’endettement important de leur firme.
Keywords: Gouvernance; desempeño financiero; discretionary power; financial performance; gobernanza; governance; latitud gerencial; latitude managériale; managerial latitude; managerial theories; performance financière; poder discrecional; pouvoir discrétionnaire; teorías gerenciales; théories managériales

Las funciones del Derecho concursal: tendencias actuales en el Derecho comparado - Moreno Buendía, Francisco Jesús (Inciso, 2021)
Las crisis económicas sufridas por la mayoría de los países industrializados han removido los cimientos del Derecho concursal, especialmente en lo que atañe a sus principios y funciones elementales. En este sentido, el aumento del volumen y de la complejidad de las estructuras empresariales ha incidido notablemente en las recientes reformas del Derecho concursal, las cuales han tratado de incentivar la función conservativa de los procedimientos concursales. El propósito de este artículo es analizar las dinámicas en la configuración de la función del Derecho concursal presentes en las recientes intervenciones legislativas llevadas a cabo por algunos países Europeos y Latinoamericanos. Para alcanzar dicho objetivo se sigue fundamentalmente un método analítico-descriptivo, a través del cual se justifica la relevancia interpretativa de la función del Derecho concursal, y se exponen las funciones tradicionales atribuidas a este sector del ordenamiento jurídico y el protagonismo de la función conservativa presente en las últimas reformas. A partir de ello, se realiza un análisis económico-funcional de esta tendencia, lo cual permite descubrir las tensiones existentes entre la función conservativa y la función solutoria. Desde esta perspectiva, se concluye sobre la necesidad de priorizar la finalidad solutoria de los procedimientos concursales, a pesar de la relevancia que actualmente se atribuye a la protección de la empresa en crisis mediante su saneamiento o rehabilitación. The financial crisis suffered by most of the industrialised have removed the foundations of bankruptcy law, especially as regards its elementary principles and functions. In this sense, the increase in the volume and complexity of business structures has had a notable impact on the recent reforms of bankruptcy law, which have tried to encourage the conservation function of bankruptcy proceedings. The purpose of this article is to analyze the dynamics in the configuration of the function of bankruptcy law present in the recent legislative interventions carried out by some European and Latin American countries. In order to achieve this objective, an analytical-descriptive method is basically used, through which the interpretative relevance of the function of bankruptcy law is justified, and it exposes the traditional functions attributed to bankruptcy law and the protagonism of the conservation function present in the latest bankruptcy reforms. From this, an economic-functional analysis of this trend is carried out, which allows to discover the tensions existing between the conservative function and the solution function of bankruptcy proceedings. From this perspective, we conclude on the need to prioritize the solution of bankruptcy proceedings, despite the relevance currently attributed to the protection of the company in difficulty through its reorganization or rehabilitation.

Les usages publics de la blockchain - De quoi les « cryptomonnaies d’État » sont-elles le nom ? - Mouchette, Julien (Revue francophone de la propriété intellectuelle, 2021)
Keywords: Intellectual property

Pourquoi les entreprises familiales au Cameroun ouvrent-elles leur capital au marché ? - Mouliom, Iliassou; Wanda, Robert (Revue de Recherches en Economie et en Management Africain, 2021)
Les débats sur le comportement de financement de l’entreprise familiale ont tendance à se complexifier au fur et à mesure de leur occurrence. La diversité des résultats qui en découlent souvent en manque d’un consensus sur le détail et le caractère influent de ses facteurs constitutifs, en témoigne à suffisance. L’objectif de cet article est donc de mettre en lumière les facteurs d’incitation du financement par les dettes de ces entreprises dont les dirigeants sont souvent reconnus pour leur frilosité à l’égard de tout ce qui engendre la perte de propriété. L’approche hypothético-déductive et la procédure de tests d’homogénéité emboîtés sont mobilisées. Il se dégage des résultats obtenus que, la tangibilité de l’actif, le coût de la dette, la rentabilité économique et financière justifient le recours à l’endettement des entreprises familiales au Cameroun.
Keywords: Comportement financier; Endettement; Entreprise familiale

Les tentatives de régulation publique des blockchains - Loi PACTE et ICOs : la régulation au service de l’attractivité - Périn-Dureau, Ariane (Revue francophone de la propriété intellectuelle, 2021)
Keywords: Intellectual property

The prospective evolution of international commercial arbitration - Purqurian, Lily Leila (Revue libre de Droit, 2021)
“It is a curious fact that the Americanization of international arbitration is a topic that is often felt but is rarely discussed.” Roger P. Alford Similar to Alford’s sentiments, the shift towards arbitration in the United States alone is a phenomenon often felt, but feebly interrogated. Law schools across the nation continue to operate under the premise of judicial decision-making grounded in “rights protection.”[1] Yet, there is a clear shift towards arbitration as the preferred procedural process, with over 303,999 cases resolved by way of arbitration in 2019 alone.[2] While this brief note does not seek to interrogate the shift towards arbitration as much as it intends to examine the impact of American arbitration on international commercial arbitration generally, that shift, as you will see, looms in the background of any and all analysis of arbitration in the United States. I will begin by briefly noting the origins- and current regime of international commercial arbitration in the United States so to address the impact of its arbitration law and arbitral institutions on arbitration globally. I will then offer thoughts on the prospective evolution of international arbitration in the United States and how that may change the directions of legal procedural processes both in the United States and abroad. I. ORIGINS- AND CURRENT REGIME OF INTERNATIONAL ARBITRATION IN THE USA As arbitration flourishes as the choice for commercial disputes, there is no doubt that the United States has become a newfound hub for arbitration. It was not always this way, however. The Federal Arbitration Act (FAA) of 1925 established a steady road to an increasingly pro-arbitration policy, in three chapters, that shows itself in case-law as: when in doubt, favor arbitration.[3] The first chapter of the FAA establishes the framework for arbitration seated in the U.S. and provides the grounds for enforceable arbitration agreements and awards, while the second and third chapters implement the 1958 New York Convention and 1975 Panama Conventions, respectively. The strictly pro-arbitration policy does not lack in its own confusion, however, because of its basis in an otherwise federalist system. The FAA has largely remained unchanged since its nascence and has thus, left a substantive amount of discretion in interpreting arbitration law in the United States to the Supreme Court. One such source of confusion in U.S. arbitration law due to a lack of amendment lies in the term “arbitrability.” Arbitrability is the susceptibility of a case to be resolved by way of arbitration. In order to define the parameters of this susceptibility, the Supreme Court has distinguished between “procedural” and “substantive” arbitrability, wherein the former concerns itself with “prerequisites such as time limits, notices, laches, estoppel, and other conditions” and the latter, with a court’s decision.[4] The benefits to arbitration remain unmatched for commercial entities, however, which inspires the aforementioned pro-arbitration policy despite any real judicial framework. Arbitration allows parties to customize their dispute resolution by choosing the venue, applicable procedural law, and an expert adjudicator who may be more familiar with the intricacies of the dispute, among other benefits. There is a commitment to secrecy that is not found in the common court and the single, binding, and final resolution of a dispute through arbitration is the precise source of criticism that inspires the flock towards arbitration. Without the federal rules of civil procedure that would otherwise govern litigation, arbitration is governed by the procedural rules that each side agrees upon. The FAA paved the way for case law in the United States that would eventually shape a stronger pro-arbitration policy than ever—counseling against “even the mildest interference by courts in the conduct of U.S.-seated arbitrations.”[5] II. THE IMPACT OF U.S. ARBITRATION LAW AND U.S. ARBITRAL INSTITUTIONS IN THE WORLD OF ARBITRATION Assessing the impact of U.S. arbitration law begins by assessing what characterizes U.S. law: civil procedure. The adversarial form of litigation in which procedural tools are employed by advocates to advance arguments in a distinct style distinguishes the United States from other countries—and this feature inevitably slipped, in some capacity, into global arbitral institutions. Because the Rules of Arbitration for the International Chamber of Commerce are so brief,[6] American lawyers had tremendous flexibility in bringing American trial procedures with them. This came specifically in the form of document production for discovery and cross-examinations “to confront adverse witnesses.”[7] Critics refer to these added procedures as costly in both time and expense, defining them as the source of the “Americanization” of arbitration. Yet, while there is truth to such criticism, it may be more accurate to acknowledge the incorporation of aspects of American trial procedure as one country’s influence on arbitration. Far from inheriting solely American practice, global arbitral institutions maintain classic procedural tools while assimilating facets of each major country’s influence on arbitration.[8] III. THE PROSPECTIVE EVOLUTION OF INTERNATIONAL ARBITRATION IN THE USA Apart from being a source of revenue,[9] international arbitration is the natural response to the increase in “trade, investment, and supply-chain relationships” that hope to live free of potential biases from domestic fora.[10] The California Supreme Court may have briefly lost sight of this when deciding Birbrower, wherein attorneys not admitted to the bar of a certain state are not only ineligible to recover attorney’s fee but also, may be fined for unauthorizing practice of law.[11] Since Birbrower over two decades ago, however, the California Legislature unanimously passed Senate Bill 766. Under SB 766, non-California lawyers are able to represent parties in international arbitration proceedings in California, bringing California to the arbitration table. As home to Silicon Valley – and even aside from big technology, home to some of the largest companies in the world – California’s SB 766 will bring a swath of arbitration proceedings to its terrain. While California may certainly work in tandem with New York as the home to arbitration for technology and privacy concerns, reserving trade and investment disputes for New York, California may very well be the next major hub of arbitration. Already, it has received massive interest in being an arbitration destination. SB 766 will transform that interest into a revenue. It thus becomes all the more important, internationally, to understand and confront the ways in which the Americanization of arbitration would take place. [1] See, e.g. Thomas E. Carbonneau, Revolution in Law Through Arbitration, The Eighty-Fourth Cleveland-Marshall Fund Visiting Scholar Lecture, 56 Clev. St. L. Rev. 233, 233 n.3 (2008), available at https://engagedscholarship.csuohio.edu/clevstlrev/vol56/iss2/3 (“judicial decision-making has shifted from rights protection to guaranteeing access to some form of adjudication. As a result, law and adjudication have become less sacramental.”) [2] See American Arbitration Association, Adr.Org, https://adr.org/ (last visited Dec. 28, 2019). [3] See, e.g., Moses H. Cone Memorial Hosp. v. Mercury Construction Corp., 460 U.S. 1, 24-25 (1983) (“[A]ny doubts concerning the scope of arbitrable issues should be resolved in favor of arbitration …”). [4] See Howsam v. Dean Witter Reynolds, Inc., 537 U.S. 79, 85 (2002) (distinguishing between “issues of substantive arbitrability [which] are for a court to decide and issues of procedural arbitrability, i.e., whether prerequisites such as time limits, notice, laches, estoppel, and other conditions precedent to an obligation to arbitrate have been met, [which] are for the arbitrators to decide.”) (citations omitted). [5] See Laurence Shore, Tai-Heng Cheng, Jenelle E. La Chuisa, Lawrence Schaner, and Mara V.J Senn, International Arbitration in the United States 1, 320 (2018). [6] George M. von Mehrem and Alana C. Jochum, Is International Arbitration Becoming Too American?, 2 Global Bus. L. Rev. 47, 51 (2011) available at https://engagedscholarship.csuohio.edu/gblr/vol2/iss1/6. [7] Id. [8] Philip J. McConnaughay, Introduction to International Commercial Arbitration in Asia 1, xxix (2002). In support of his assertion, McConnaughay reports that from 1995 to 2000, China’s leading international arbitration commission, CIETAC, received 4,200 new international commercial arbitrations and the Hong Kong International Arbitration Centre (HKIAC) received 1,394, totaling 5,594. Id. Note: interrogatories and depositions are not included. [9] See ICC (International Chamber of Commerce), ICC Arbitration Figures Reveal New Record for Awards in 2018, https://iccwbo.org/media-wall/news-speeches/icc-arbitration-figures-reveal-new-record-cases-awards-2018/. [10] Daily Journal, International Arbitration Finally Comes to California, Howard B. Miller, https://www.dailyjournal.com/mcle/330-international-arbitration-finally-comes-to-california. [11] See generally, Birbrower, Montalbano, Condon & Frank v. Superior Court, 17 Cal. 4th 119 (1998).
Keywords: Arbitrage; Arbitragem; Arbitration; Commercial dispute; International Arbitration

Droit américain des brevets : sa surprenante expansion en dehors du territoire américain - Signore, Philippe; McBride, Steve (Revue francophone de la propriété intellectuelle, 2021)
La fabrication, l’utilisation et la vente aux États-Unis d’un produit couvert par un brevet américain, sans l’autorisation du breveté, constitue une contrefaçon de ce brevet. Toutefois, certains développements législatifs et des décisions de justice rendues ces dernières années ont montré que la portée d’un brevet américain pouvait être étendue à des activités se produisant en dehors du territoire américain. The unauthorized making use or sale within the United States of a product covered by a U.S. patent infringes the patent. However, in many cases damages and liability for infringing U.S. patents can extend beyond purely domestic uses to cover activities taking place far outside the United States. U.S. patents may cover activities that have little or nothing to do with the United States. Many companies are unaware of this surprisingly broad geographic reach. This article reviews such activities.
Keywords: Intellectual property

Harmonization (or rather Standardization) of Cooperative Law in the OHADA Zone: What is the Result after Ten Years of Implementation of the Uniform Act? - Tadjudje, Willy (CIRIEC - España. Revista jurídica de economía social y cooperativa, 2021)
The Uniform Act related cooperative societies (UA-COOP) is the main source of cooperative law in all the seventeen States parties to the OHADA founding Treaty. Ten years after its entry into force (2011-2021), the aim of this study is to assess the level of enforcement of this Act. More concretely, the aim is to compare the state of cooperative law at the time of the entry into force of the UA-COOP (2011) with the current situation (in 2021). Such a comparison should make it possible to assess the contribution of the UA-COOP to the development of cooperative law and strengthening of national cooperative movements in the OHADA zone.

Le nouveau droit OHADA de l’insolvabilité : un droit debtor friendly ? - Takafo-Kenfack, Didier; Notué, Chrislert Noël (Revue de la recherche juridique, 2021)
L'Acte uniforme sur les procédures collectives d’apurement du passif révisé a considérablement amélioré la situation du débiteur à travers le renforcement des mesures de sauvetage et la légitimation du droit au rebond qui lui permet sous certaines conditions de bénéficier de la purge de ses dettes. Ce changement de paradigme devrait absolument tenir compte des intérêts des créanciers qui attendent désespérément le règlement de leurs créances. L’ambition de la présente étude est de démontrer que malgré le vent de la modernité, le législateur OHADA n’en a pas tenu compte dans la dernière réforme de la matière collective au vu de l’importance des ajustements qui profitent principalement au débiteur. Ce renforcement des mesures de protection en faveur d’un seul protagoniste n’augure pas des lendemains meilleurs dans un espace juridique où les États membres n’ont pas la culture, encore moins des possibilités de consentir facilement aux entreprises nécessiteuses, des crédits comparables à ceux régulièrement obtenus des créanciers.
Keywords: Créancier; Insolvency; Procédures collectives; Rebond; débiteur

Le retour de l’opposabilité du droit d’auteur sur Internet : étude de l’article 17 de la Directive DAMUN - Treppoz, Edouard (Revue francophone de la propriété intellectuelle, 2021)
Keywords: Intellectual property

La politique et la propriété intellectuelle - Vanbrabant, Bernard (Administration Publique : Revue du Droit Public et des Sciences Administratives, 2021)

L’accompagnement de l’entrepreneuriat féminin dans les pays africains en développement - Zogning Nguimeya, Joseph Félix (Revue Organisations & territoires, 2021)
Les femmes entrepreneures se heurtent à de nombreux obstacles pour mener à bien leur processus d’entrepreneuriat dans les pays en développement. Ces obstacles sont associés à une faible inclusion financière ainsi qu’à des normes et cultures spécifiques qui définissent les rôles des femmes dans la société. Les résultats de notre étude montrent que les programmes mis en oeuvre pour accompagner l’entrepreneuriat féminin s’attellent davantage à la promotion de l’entrepreneuriat, plutôt que de s’attaquer aux causes de l’écart observé entre les hommes et les femmes dans le succès entrepreneurial.

国际商事仲裁费用构成及合理控制仲裁费用探索 - 侯, 进才 (Journal of Oil and Gas Technology, 2021)
仲裁作为解决国际商事争议的主要方式之一，受到国际工程承包企业的青睐，然而当事人在决定一个案件是否要提起仲裁时，常会把仲裁费用作为一个重要考量指标，高昂的仲裁费用可能会限制国际商事仲裁制度的健康发展。本文以2017版国际商会仲裁规则下的收费标准为基础，从仲裁费用的构成、计算方法入手，探讨了仲裁费用影响因素，并给出了控制仲裁过程费用的合理化建议。 Arbitration, as one of the main ways to resolve international commercial disputes, remains a popular choice for international engineering company. The arbitration fees will be an important evaluating indicator when the parties considering apply for arbitration. Expensive arbitration fees may restrict the healthy development of international commercial arbitration system. Based on the arbitration cost and fees under the arbitration rules of the 2017 edition of the International Chamber of Commerce, characteristics, composition and calculation method of the arbitration fees are showed in this paper firstly; then, its influencing factors are discussed. Reasonable suggestions for controlling the arbitration fees are given in the end of this paper.
Keywords: Arbitrage; Arbitragem; Arbitraje; Arbitration; Arbitration Fees; Composition of Arbitration Fees; Controlling the Arbitration Fees; International Commercial Disputes; 仲裁费用; 国际商事; 控制费用; 费用构成